CONDUCTIVE MEMBER, PROCESS CARTRIDGE AND ELECTROPHOTOGRAPHIC IMAGE FORMING APPARATUS
The conductive member with a matrix-domain structure and platinum electrode enhances charge transfer efficiency, addressing the challenge of maintaining high image quality and durability in high-speed electrophotographic processes.
Patent Information
- Application Number
- JP2020174641
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-18
- Filing Date
- 2020-10-16
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2040-10-16
AI Technical Summary
Existing electrophotographic apparatuses face challenges in maintaining high image quality and durability during high-speed processes due to insufficient charge supply to toner, leading to issues like foggy images and uneven charge distribution.
A conductive member with a support, conductive layer, and surface layer is designed, featuring a matrix with crosslinked rubbers and dispersed domains, along with a platinum electrode, to ensure efficient charge transfer and distribution, characterized by specific impedance measurements and domain structure configurations.
The conductive member effectively suppresses variations in charge supply, ensuring high-quality image output and durability even in high-speed processes by maintaining consistent charge transfer and distribution.
Smart Images

Figure 0007599897000047 
Figure 0007599897000048 
Figure 0007599897000049
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a conductive member used in an electrophotographic image forming apparatus, a process cartridge having the conductive member, and an electrophotographic image forming apparatus. [Background technology]
[0002] An electrophotographic image forming apparatus (hereinafter also referred to as an "electrophotographic apparatus") has conductive members such as a developing roller, a toner supply roller, a charging roller, a transfer roller, and a developing blade. 5 ~1×10 12 Conductive members having a conductive layer with an electrical resistance value (hereinafter referred to as "resistance value") such as Ω are used. Conventionally, electronic conductive agents such as carbon black and ionic conductive agents such as quaternary ammonium salts have been used to impart conductivity to the conductive layer and form a stable conductive mechanism. Conductive members are required to have various functions, such as transporting toner to an electrophotographic photoreceptor (hereinafter referred to as "photoreceptor"), charging the photoreceptor, imparting a charge to the toner, and preventing surface contamination, and various measures have been disclosed to achieve these functions.
[0003] Among them, the developer carrier is 10 3 ~10 10 Elastic rollers with an electrical resistance of Ω·cm are generally used. In addition, in view of the demand for even higher durability of developer carriers and even higher image quality of electrophotographic images, developer carriers with a surface layer provided on the surface of the elastic layer are now being used.
[0004] Patent Document 1 discloses a method for improving the toner releasability and wear resistance by using a roll-shaped developer carrier having a continuous phase and a discontinuous phase on the surface. A conductive member for electrophotographic equipment is disclosed that has a conductive / non-conductive continuous phase and a discontinuous phase and thereby has low hardness, low settling and excellent charging properties.
[0005] Furthermore, Patent Document 2 discloses a method for reducing uneven discharge by having a surface layer of a conductive member have a matrix-domain structure consisting of a non-conductive sea portion and island portions containing an electronic conductive agent. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2017-15800 A [Patent Document 2] JP 2011-22410 A Summary of the Invention [Problem to be solved by the invention]
[0007] In recent years, electrophotographic apparatuses are required to maintain high image quality and high durability even in high-speed processes in harsh environments. For example, when an electronic conductive agent such as carbon black is dispersed in a conductive layer, the electrical charge moves through the conductive path that connects the electronic conductive agent from the conductive support to the surface of the conductive member, and electrical conductivity is exhibited. Therefore, since this conductive path is responsible for transporting the electrical charge consumed by the current flow, a certain amount of time is required before the electrical charge can be supplied for the next current flow. In the case of developing members, in a high-speed process, if the charge applied to the toner cannot keep up with the process speed, the amount of charge applied to the toner varies, making it difficult to achieve uniform development, and for example, there are cases where fogged images occur due to toner with a low charge amount.
[0008] In addition, conductive members that exhibit conductivity by dispersing ion conductive agents in a conductive layer exhibit conductivity by the movement of anions and cations such as quaternary ammonium. Therefore, in a high-speed process, if the movement speed of anions and cations is slow, they cannot keep up with the process speed, and as mentioned above, the supply of charge to the toner for the next development is insufficient, which can cause fogged images.
[0009] One aspect of the present disclosure is to provide an electrophotographic conductive member capable of maintaining high image quality and high durability even in a high-speed process. Another aspect of the present disclosure is to provide an electrophotographic image forming apparatus capable of stably outputting high-quality electrophotographic images and a process cartridge used therein. [Means for solving the problem]
[0010] According to one aspect of the present disclosure, A conductive member for electrophotography comprising a support having a conductive outer surface, a conductive layer provided on the outer surface of the support, and a surface layer provided on the outer surface of the conductive layer, the conductive layer has a matrix containing a crosslinked product of a first rubber and a plurality of domains dispersed in the matrix, The domain contains a crosslinked product of a second rubber and an electronic conductive agent. A platinum electrode is provided directly on the outer surface of the conductive layer. An AC voltage with an amplitude of 1 V and a frequency of 1.0×10 is applied between the outer surface of the support and the platinum electrode in an environment of a temperature of 23° C. and a relative humidity of 50%. -2 Hz~1.0×10 7 The impedance was measured by applying a voltage varying between 1.0 x 10 Hz. The frequency was plotted on the horizontal axis and the impedance on the vertical axis in logarithmic scale. 6 Hz~1.0×10 7 The slope in Hz is -0.8 to -0.3 and the frequency is 1.0 x 10 -2 Hz~1.0×10 1 Impedance at Hz is 1.0×10 4 ~1.0×10 11 Ω, A platinum electrode was provided directly on the outer surface of the conductive member, and an AC voltage with an amplitude of 1 V and a frequency of 1.0×10 was applied between the outer surface of the support and the platinum electrode in an environment of a temperature of 23° C. and a relative humidity of 50%. -2 Hz~1.0×10 7 The impedance was measured by applying a voltage varying between 1.0 x 10 Hz. The frequency was plotted on the horizontal axis and the impedance on the vertical axis in logarithmic scale. -2Hz~1.0×10 1 Impedance at Hz is 1.0×10 5 ~1.0×10 11 A conductive member is provided which is Ω.
[0011] According to another aspect of the present disclosure, there is provided a process cartridge configured to be detachably mountable to a main body of an electrophotographic image forming apparatus, the process cartridge including the above-mentioned conductive member. Furthermore, according to another aspect of the present disclosure, there is provided an electrophotographic image forming apparatus including the above-mentioned conductive member. Effect of the Invention
[0012] According to one aspect of the present disclosure, there is provided a conductive member for electrophotography capable of maintaining high image quality and high durability even in a high-speed process. According to another aspect of the present disclosure, there is provided an electrophotographic image forming apparatus capable of stably outputting high-quality electrophotographic images, and a process cartridge used therein. [Brief description of the drawings]
[0013] [Figure 1] 1 is a schematic cross-sectional view of a conductive roller for electrophotography according to an embodiment of the present disclosure. [Diagram 2] 1 is a schematic cross-sectional view of an electrophotographic development blade according to an embodiment of the present disclosure. [Diagram 3] FIG. 1 is an explanatory diagram of a graph of impedance characteristics. [Figure 4] FIG. 13 is an explanatory diagram of impedance behavior. [Diagram 5] FIG. 1 is a schematic diagram of a matrix-domain structure. [Figure 6] FIG. [Figure 7] FIG. [Figure 8] FIG. 2 is a schematic diagram of a process cartridge. [Figure 9] FIG. 1 is a schematic diagram of an electrophotographic apparatus. [Figure 10]FIG. 2 is a schematic diagram showing a state in which measurement electrodes are formed on a conductive roller (conductive layer surface). [Figure 11] FIG. 1 is a cross-sectional view showing a state in which a measurement electrode is formed on the surface of a conductive roller (surface layer). [Figure 12] FIG. 4 is a conceptual diagram illustrating the size of protrusions on the surface layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The movement of charges in the conductive paths of the conductive layer in the conventional developing member and the process of imparting charges to the toner are assumed to be as follows. First, a voltage is applied to the conductive support connected to a power source, and an electric charge is supplied to the conductive support, which is then transported (supplied) to the surface of the developing member through the conductive layer of the conductive member. When the surface of the developing member comes into contact with the toner in this state, the charge on the surface of the developing member is transferred to the toner, that is, the charge is supplied to the toner. The charge on the surface of the developing member is reduced by the amount of toner transferred thereto, but as long as the conductive support of the developing member is connected to a power source, new charge is supplied to the surface of the developing member through the conductive support. In this manner, new charges are continuously supplied to the developing member, so that the toner can be continuously charged.
[0015] On the other hand, in a development process using a development roller or a development sleeve and a development blade, the toner particles form a toner layer having a thickness of about 2 to 3 particles on the surface of a toner carrier, and are developed onto a photoconductor.
[0016] In a two-layer developing member having a surface layer on a conductive layer, the toner particles are charged mainly by frictional charging between the surface layer of the developing member and the toner particles.
[0017] On the surface of the toner carrier, the toner is charged by receiving electric charge from the toner carrier within the very short time it passes between the toner carrier and the developing blade while rolling. Therefore, the electric charge lost from the surface layer due to the frictional charging of the toner must be quickly supplied from the elastic layer.
[0018] Therefore, if the supply of charge in the elastic layer stagnates and the charge transfer speed to the surface layer of the developing member is slow, the amount of new charge supplied to the surface of the developing member is limited. In a high-speed process that requires a large amount of charge to be supplied to toner per unit time, if the amount of new charge supplied to the surface layer of the developing member is limited, a shortage of charge supply to the toner occurs. As a result, the amount of charge received during contact with the surface of the developing member and rolling occurs to vary, and the charge distribution of the toner becomes large. Furthermore, toner moves to the photoconductor without control in the developing section (the position where the photoconductor and the developing member face each other), which makes it easy for so-called fogging to appear.
[0019] The present inventors have attempted to lower the resistance of the conductive layer by blending a large amount of a conductive agent in the conductive layer in order to increase the charge transfer rate of the conductive layer to the surface layer of the developing member. However, whether an ionic conductive agent or an electronic conductive agent is used, the effect of reducing the proportion of toner that is not sufficiently charged in the developing section of a high-speed process is small, and the expected effect of reducing fog was not obtained. As described above, it is not easy to provide a developing member capable of forming high-quality images even in a high-speed process. According to the study by the present inventors, the conductive roller according to Patent Document 1 and the conductive roller according to Patent Document 2 sometimes generated fogged images, which are considered to be due to an insufficient amount of charge supply, in image evaluation in a high-speed process. The present inventors have conducted extensive research to solve the problems described above. In the case of a developing member used to impart charge to a toner, the conductive mechanism for imparting charge to the toner has conventionally been a conductive path of an electronic conductive agent such as carbon black or a conductive path of an ionic conductive agent, as described above. When a voltage is applied, the charge is transported to the surface of the developing member via a conductive path, and an electric field is generated between the toner and the developing member. Furthermore, at the contact surface between the developing member surface and the toner, the electric field causes the charge to move from the developing member surface to the toner. The toner is usually carried on the developing member surface as a toner layer having a thickness of 2 to 3 particles, and is supplied with charge when it comes into contact with the developing member while rolling.
[0020] In addition, the contact area between the toner and the developing member has a certain area. Within this area, the toner is charged multiple times. For example, in a case where a developing device has a developing roller and a developing blade, the toner is charged multiple times while passing through the contact area with the developing blade due to the rotation of the developing roller and the rolling of the toner. Once charge transfer occurs, the charge transfer supplied from the surface of the developing member continues for a certain period of time, and the charge transported to the surface of the developing member is consumed. When the charge transfer ends, the consumed charge is again supplied from the conductive path inside the developing member to the surface of the developing member, and the next charge transfer occurs. Therefore, the final charge amount of the toner is considered to be the sum of the charge amounts transferred multiple times. As described above, the toner environment and development history affect the amount of charge imparted at the contact portion with the surface of the developing member, so that the amount of charge on the toner usually has a distribution. In particular, in the case of a high-speed process, after the first charge is imparted to the toner, the supply of the charge amount for the next charge imparting may not be able to keep up. In particular, the first charge imparted immediately after entering the development nip region formed by the developing blade and the developing member has a sufficient amount of charge, but the charge supply for the subsequent charge imparting may not be able to keep up.
[0021] Therefore, the present inventors have conducted extensive research to obtain a conductive member capable of storing a sufficient amount of charge in a short period of time and quickly supplying the charge, and have found that a conductive member having the following configuration satisfies the above requirements.
[0022] The conductive member includes a support having a conductive outer surface, a conductive layer provided on the outer surface of the support, and a surface layer provided on the outer surface of the conductive layer; The conductive layer has a matrix containing a cross-linked product of a first rubber and a plurality of domains dispersed in the matrix, and the domains contain a cross-linked product of a second rubber and an electronic conductive agent. In order to measure the impedance of the conductive layer, a platinum electrode is directly provided on the outer surface of the conductive layer, and an AC voltage with an amplitude of 1 V is applied between the outer surface of the support and the platinum electrode in an environment of a temperature of 23° C. and a relative humidity of 50%. -2 Hz~1.0×10 7 A voltage is applied while changing the frequency between 0.01 V and 0.1 V. When the measurement results are plotted in a double logarithmic scale with frequency on the horizontal axis and impedance on the vertical axis, the conductive layer according to this embodiment satisfies both the following first and second requirements.
[0023] <First requirement> Frequency 1.0×10 6 Hz~1.0×10 7 The slope in Hz is greater than or equal to -0.8 and less than or equal to -0.3. <Second requirement> Frequency is 1.0×10 -2 Hz~1.0×10 1 Impedance at Hz is 1.0×10 4 ~1.0×10 11 It is Omega.
[0024] Furthermore, a platinum electrode is provided directly on the outer surface of the conductive member, i.e., the outer surface of the surface layer, and the impedance between the outer surface of the support and the platinum electrode is measured under the same conditions as above. The measurement results are plotted logarithmically with frequency on the horizontal axis and impedance on the vertical axis, and the frequency is 1.0×10 -2 Hz~1.0×10 1 Impedance at Hz is 1.0×10 5 ~1.0×10 11 It is Omega.
[0025] That is, the conductive member according to the present embodiment enables a development process in which the variation in the charge amount of the toner is very small. Furthermore, since the conductive member according to the present disclosure has a surface layer as the outermost layer, it is possible to maintain the development process in which the variation in the charge amount of the toner is very small for a long period of time. In this disclosure, 1.0×10 -2 Hz~1.0×10 1 The Hz frequency range is sometimes called the "low frequency range."
[0026] The conductive member according to this embodiment will be described below using a developing roller as an example. Note that the conductive member according to this embodiment is not limited to the developing roller, and may also be applied to, for example, a charging roller, a fixing roller, a developing blade, and a toner supply roller. The conductive member according to this embodiment includes a support having a conductive outer surface, a conductive layer provided on the outer surface of the support, and a surface layer provided on the outer surface of the conductive layer. The conductive layer is conductive. Here, the conductive layer is defined as a layer having a volume resistivity of 1.0×10 8 The electrical resistance is defined as less than Ωcm. The conductive layer has a matrix containing a cross-linked product of a first rubber and a plurality of domains dispersed in the matrix, and the domains contain a cross-linked product of a second rubber and an electronic conductive agent. The conductive layer of the conductive member satisfies the above-mentioned <first requirement> and <second requirement>.
[0027] <First requirement> The first requirement stipulates that charge stagnation in the conductive member is unlikely to occur on the high frequency side. When the impedance of the conductive layer of a conventional conductive member is measured, the slope is always -1 on the high frequency side. Here, the slope refers to the slope with respect to the horizontal axis when the impedance characteristics of the conductive member are plotted against frequency in a double logarithmic manner, as shown in Figure 3. The equivalent circuit of the conductive layer in the conductive member is expressed as a parallel circuit with electrical resistance R and capacitance C, and the absolute value of the impedance |Z| can be expressed by the following formula (1), where f represents the frequency.
[0028]
number
[0029] On the high frequency side, the impedance becomes a straight line with a slope of -1. This can be inferred to be a state in which the movement of the charge cannot keep up with the high frequency voltage and stagnates, causing the electrical resistance value R to increase significantly; in other words, the capacitance of the insulation is being measured. The state in which the charge stagnates can be inferred to be a state in which R in equation (1) approximates infinity. In this case, the denominator element (R -2 +(2πf) 2 C 2 ) in R -2 (2πf) 2 C 2 Therefore, equation (1) can be approximated as R -2 Finally, by taking the logarithm of both sides of equation (2), we obtain equation (3), where the slope of logf becomes -1.
[0030]
number
[0031] The meaning of the above formulas (1) to (3) will be explained with reference to FIG. 4. In FIG. 4, the vertical axis indicates the logarithm of the absolute value of the impedance (log|Z|), and the horizontal axis indicates the logarithm of the frequency of the measured oscillating voltage (logf). FIG. 4 shows the behavior of the impedance expressed by formula (1). First, as explained above, the absolute value of the impedance satisfying formula (1) decreases at a certain frequency as the frequency increases. In addition, in a double logarithmic plot such as that in FIG. 4, the decreasing behavior is a straight line with a slope of -1, as shown in formula (3), regardless of the electrical resistance value or electrostatic capacitance of the conductive member. When the impedance characteristics of an insulating resin layer are measured, they become a straight line with a slope of -1. Therefore, when measuring the impedance of the conductive layer of a conductive member, a state where the slope is -1 is presumably a state where the movement of charge stagnates on the high frequency side. When the movement of charge stagnates on the high frequency side, it is not possible to keep up with the frequency of the charge supply to the surface layer in a high-speed process. As a result, there are times when the charge cannot be supplied, which is presumably causing variations in the amount of charge on the toner.
[0032] On the other hand, in the conductive member according to the present embodiment, the impedance gradient of the conductive layer is 1.0×10 6 Hz~1.0×10 7 In the high frequency range of 100 Hz, the impedance is between -0.8 and -0.3, so the supply of electric charge is less likely to stagnate on the high frequency side. As a result, it is possible to supply electric charge from the low frequency range where the impedance is a constant value to the high frequency range, especially on the high frequency side where the movement of electric charge is likely to stagnate. Since the charge supply can be realized abundantly in a wide frequency range, the variation in the charge supply to the surface layer can be suppressed, and the total amount of toner charge can be improved. The high frequency range is the range of the charge supply generated from the conductive member with the highest frequency, and therefore it is considered to be a range in which the variation in the charge supply to the surface layer is likely to occur. By showing the above range of values in which the slope is greater than -1 in such a frequency range, a slope greater than -1 is also obtained in a high frequency range lower than the frequency range. As a result, the variation in the charge supply to the surface layer can be suppressed, and the total amount of toner charge can be improved through the surface layer. As the process speed increases, it is necessary to increase the frequency of the charge supply and the number of charge supplies. 6 Hz~1.0×10 7 Control of charge delivery and conduction mechanisms at high frequencies such as the Hz range is important.
[0033] As described above, in order to increase the number of times charge is supplied to the toner through the surface layer, it is effective to deviate the impedance slope of the conductive layer in the high frequency region from -1. This makes it possible to effectively achieve the characteristic of quickly supplying charge to the toner and then the charge for the next charge supply. The impedance slope deviating from -1 means that the supply of charge in the conductive member is not stagnating, and therefore such a conductive member can obtain a characteristic in the direction of suppressing the variation in the charge supply to the toner.
[0034] <Second requirement> The impedance in the low frequency range related to the second requirement represents a characteristic in which charge stagnation is unlikely to occur. This can also be seen from the fact that the impedance slope on the low frequency side is not in the -1 range. In addition, in the above formula (1), when the frequency f is approximated to zero, it can be approximated to the electrical resistance value R, and therefore it can be seen that the electrical resistance value R represents the ability of electric charges to move in a single direction. Therefore, it can be assumed that measurements made while applying a low-frequency voltage simulate the amount of charge movement in a state where the movement of the electric charges can follow the voltage oscillation. The amount of charge transfer at low frequencies is an index of the ease of charge transfer between the conductive layer of the conductive member and the measurement electrode (platinum electrode), and can also be an index of the amount of charge that can be transferred from the conductive layer of the conductive member to the surface layer by passing current at the interface. Moreover, the amplitude of the AC voltage used in measuring the impedance according to the first and second requirements is 1 V. This oscillating voltage for measurement is significantly lower than the voltage actually applied to a conductive member in an electrophotographic image forming apparatus, which is several hundreds to several thousands of V. Therefore, it is considered that the ease with which a charge is released from the conductive layer surface of a conductive member can be evaluated at a higher level by measuring the impedance according to the first and second requirements.
[0035] In addition, by satisfying the second requirement, it is possible to control the ease of charge generation within an appropriate range. 4If the impedance is lower than Ω, the amount of charge supplied at one time becomes too large, and the supply of charge for the next charge supply cannot keep up, which works in the direction of causing variations in the charge supply and makes it difficult to suppress fogging. 11 If it exceeds Ω, the ease of discharging electric charge decreases, and the amount of current flow does not reach a level sufficient to compensate for the variation in the supply of electric charge. As explained in FIG. 4, the absolute value of the impedance in the low frequency range is constant in the conductive layer of the conductive member. -2 Hz~1.0×10 1 The impedance in Hz can be substituted with the impedance value at a frequency of, for example, 1 Hz. A conductive layer that satisfies both the first and second requirements can suppress the variation in charge supply to the surface layer in the frequency range from the low frequency side to the high frequency side, thereby reducing fogging. By satisfying the first requirement, the variation in charge supply on the high frequency side can be suppressed. Furthermore, by satisfying the second requirement, the amount of supplied charge is further improved, and the occurrence of fogging can be effectively suppressed.
[0036] <Method of measuring impedance> The impedance can be measured by the following methods. When measuring impedance, it is necessary to eliminate the effect of contact resistance between the conductive layer and the measurement electrode. For this purpose, a low-resistance thin-film of platinum is deposited directly on the outer surface of the conductive layer, and the thin film is used as an electrode. It is also preferable to measure impedance with two terminals, with the conductive support as the ground electrode. Examples of the method for forming the electrode include metal vapor deposition, sputtering, application of a metal paste, application of a metal tape, etc. Among these, a method for forming an electrode by vapor deposition of a platinum thin film is preferred from the viewpoint of reducing the contact resistance with the outer surface of the conductive layer. When forming a platinum thin film directly on the outer surface of a conductive layer, it is preferable to provide a mechanism for holding a conductive member to the vacuum deposition apparatus, in consideration of the ease of forming the thin film and the uniformity of the thin film. For a conductive member having a cylindrical cross section, it is preferable to use a vacuum deposition apparatus further provided with a rotation mechanism. It is preferable to form a platinum thin-film electrode with a width of about 10 mm in the longitudinal direction of the conductive member, and connect a metal sheet wrapped around the platinum thin-film electrode in a direction intersecting the longitudinal direction without any gaps to a measurement electrode extending from a measuring device to perform the measurement. In the case of a cylindrical conductive member, it is preferable to use a metal sheet wrapped around the circumferential direction of the conductive layer without any gaps. This makes it possible to perform impedance measurement without being affected by the fluctuation of the size of the outer edge (outer diameter in the case of a cylindrical conductive member) in the cross section perpendicular to the longitudinal direction of the conductive layer or the surface shape. As the metal sheet, aluminum foil, metal tape, etc. can be used. Impedance measurement devices include impedance analyzers, network analyzers, spectrum analyzers, etc. 7 Any device capable of measuring impedance in a frequency range up to the order of Hz may be used. Among these, it is preferable to measure using an impedance analyzer, since it is in the range of electrical resistance of the conductive member. The measurement conditions for impedance will now be described. Using an impedance measurement device, 1.0 x 10 -2 Hz~1.0×10 7 Impedance is measured in the Hz frequency range. Measurements are performed in an environment with a temperature of 23°C and a relative humidity of 50%. In order to reduce measurement variation, five or more measurement points are provided per digit of frequency, and the vibration voltage is 1Vpp. Regarding the measurement voltage, a DC voltage may be applied in consideration of the voltage applied to the conductive member in the electrophotographic apparatus. Specifically, it is preferable to perform measurement while applying a DC voltage of 10 V or less in combination with an oscillating voltage in order to quantify the characteristics of charge transport and accumulation.
[0037] Next, a method for calculating the impedance gradient will be described. Using commercially available spreadsheet software, plot the absolute impedance values against the measurement frequency on a log-log graph. 6 ~1.0×10 7 The slope of the absolute value of impedance in the frequency domain of Hz is 1.0 x 10 6 ~1.0×10 7 This can be determined by using the measurement points in the Hz frequency range. Specifically, the linear approximation line of the graph plot in the frequency range is calculated using the least squares method, and the slope of the line is calculated. Next, 1.0×10 -2 ~1.0×10 1 The arithmetic average value at the measurement points in the low frequency range of 100 Hz is calculated, and the obtained value is taken as the impedance on the low frequency side. In measuring the impedance gradient, the conductive member is divided into five equal parts in the longitudinal direction, and measurements are made at five arbitrary locations within each of the five regions, and the arithmetic average of the measured values of the gradient at the five locations is calculated.
[0038] Furthermore, the conductive member of this embodiment has a frequency of 1.0×10 -2 Hz~1.0×10 1 Impedance at Hz is 1.0×10 5 ~1.0×10 11 The impedance at the outer surface of the conductive member is measured in the same manner as the impedance at the outer surface of the conductive layer, and is similarly plotted log-logarithmically.
[0039] As described above, in the conductive member of this embodiment, the conductive layer satisfies the first and second requirements, so that the movement of charges is less likely to stagnate and a sufficient amount of charge can be supplied to the surface layer. As with the second requirement of the conductive layer, when the frequency f in formula (1) is approximated to zero, the electrical resistance value R can be approximated, and the electrical resistance value R represents the ability of charge to move in a single direction. Therefore, it can be assumed that a measurement performed while applying a low-frequency voltage with a platinum electrode provided on the outer surface of the conductive member simulates the amount of charge movement in a state where the charge movement can follow the voltage oscillation. The amount of charge movement at low frequencies is an index of the ease of charge movement between the surface layer of the conductive member and the measurement electrode, and can also be an index of the amount of charge that can be moved from the surface layer of the conductive member to the toner by contact.
[0040] The impedance in the above low frequency range measured on the outer surface of the conductive member is 1.0 x 10 5 ~1.0×10 11 The resistance Ω indicates that the charge supplied without stagnation from the conductive layer is also supplied without stagnation to the toner through the surface layer. In order to resupply the charge supplied from the conductive layer to the toner from the surface layer without stagnation, it is necessary to adjust the volume resistivity of the surface layer within a suitable range. By using a surface layer material with an appropriate volume resistivity, the impedance in the above low frequency range can be reduced to 1.0×10 5 ~1.0×10 11 It can be Ω.
[0041] (Surface layer) The charge on the surface layer of the toner that has been lost as a result of the frictional charging is continuously supplied from the conductive layer that satisfies the above-mentioned <first requirement> and <second requirement>. In order to resupply the charge from the conductive layer to the toner from the surface layer without stagnation, the volume resistivity of the surface layer must be 1.0×10 4 Ω cm or more, 1.0×10 15 It is preferable that the resistivity is Ω·cm or less. The volume resistivity of the surface layer is 1.0×10 4When the surface resistivity is Ω·cm or more, the charge generated by friction with the toner leaks to the surface layer side, which can prevent the charge supply to the toner from becoming insufficient. In addition, the surface layer has a volume resistivity of 1.0×10 15 When the resistivity is Ω·cm or less, the amount of charge transfer in the surface layer can be sufficiently ensured, and the supply of charge to the toner does not become insufficient. In either case, the impedance in the low frequency range measured on the outer surface of the conductive material is 1.0 x 10 5 ~1.0×10 11 It is possible to set it to Ω.
[0042] <Volume resistivity measurement method> The volume resistivity of the surface layer of the conductive member can be measured by the following method. The volume resistivity of the surface layer can be measured using an atomic force microscope (AFM) in a conductive mode. First, the surface layer of the conductive member is cut into a sheet piece using a manipulator, and metal is vapor-deposited on one side of the surface layer. A DC power source is connected to the metal-deposited surface, voltage is applied, and the free end of a cantilever is brought into contact with the other side of the surface layer, and a current image is obtained through the AFM body. The current value at 100 randomly selected points on the surface is measured, and the volume resistivity can be calculated from the average current value at the top 10 points with the lowest measured current values, the average film thickness, and the contact area of the cantilever.
[0043] (1) Conductive materials The electroconductive member for electrophotography according to this embodiment has a conductive support, at least one conductive layer on the support, and a surface layer provided on the outer surface of the conductive layer.
[0044] As an example, a roller-shaped conductive member (developing roller) is shown in Fig. 1. The developing roller 1A shown in Fig. 1(a) has a conductive support 2, a conductive layer 3 provided on its outer circumferential surface (outer surface), and a surface layer 4 on the outer circumferential surface of the conductive layer 3. The layer configuration of the developing roller 1A is not limited to the form shown in Fig. 1(a). Another form of the developing roller 1 may be a developing roller 1A' having a base layer (resin layer) 5 between a support 2 and a conductive layer 3 provided on the outer peripheral surface thereof as shown in Fig. 1(b). Further examples include developing rollers having an intermediate layer (not shown) between the conductive layer 3 and the surface layer 4 of the developing rollers 1A and 1A'.
[0045] Another example of the conductive member is a blade-shaped member (developing blade). Fig. 2 is a schematic cross-sectional view of a developing blade 1B. The developing blade 1B shown in Fig. 2 is composed of a conductive support 2, a conductive layer 3 provided in a partial region including the end of the outer surface of the support 2, and a surface layer 4 provided on the outer peripheral surface of the conductive layer 3. The developing blade 1B can also be configured such that the conductive layer 3 is coated on the tip end of a conductive stainless steel sheet that forms part of the support, and the rear end of the stainless steel sheet is welded to the conductive support 2. The conductive member according to the present disclosure can be used as an electrophotographic member such as a developing roller, a charging roller, a developing sleeve, a fixing roller, a developing blade, and a toner supply roller. The configuration of the conductive member according to one embodiment of the present disclosure will be described in detail below.
[0046] <Conductive support> The conductive support 2 functions as a support member for the conductive member and, in some cases, as an electrode. Regarding specific examples of the support, when the conductive member is in the form of a roller, the support 2 is in the form of a solid column or a hollow cylinder, and when the conductive member is in the form of a blade, the support 2 is in the form of a thin plate. The material constituting the conductive support can be appropriately selected from those known in the field of conductive members for electrophotography and those usable as such developing members. Examples include metals or alloys such as aluminum and stainless steel, carbon steel alloys, conductive synthetic resins, iron, and copper alloys. Furthermore, these may be subjected to oxidation treatment or plating treatment with chromium, nickel, etc. As the type of plating, either electric plating or electroless plating can be used. From the viewpoint of dimensional stability, electroless plating is preferred. As the type of electroless plating used here, nickel plating, copper plating, gold plating, and other various alloy platings can be mentioned. The plating thickness is preferably 0.05 μm or more, and considering the balance between work efficiency and anti-rust ability, the plating thickness is preferably 0.1 to 30 μm. If a medium resistance layer or an insulating layer exists between the support and the conductive layer, it becomes impossible to quickly supply electric charge after the electric charge is consumed by current flow. Therefore, it is preferable that the conductive layer is provided directly on the support, or that the conductive layer is provided on the outer periphery of the support via only a base layer made of a thin conductive resin layer such as a primer. As the primer, a known one can be selected and used depending on the rubber material for forming the conductive layer and the material of the support, etc. Examples of the primer material include thermosetting resins and thermoplastic resins, and specifically, materials such as phenolic resins, urethane resins, acrylic resins, polyester resins, polyether resins, and epoxy resins can be used. The impedance measured by providing a platinum electrode on the outer surface of the conductive resin layer in the same manner as the conductive layer was 1.0×10 -5 ~1.0×10 1 It is preferably in the range of Ω. If the support with the resin layer has an impedance in the above range in the low frequency range, sufficient charge can be supplied to the conductive layer, and the matrix-domain structure contained in the conductive layer is preferably such that the function of suppressing the loss of charge supply due to the first and second requirements is not impaired. The impedance at the outer surface of the resin layer can be measured by the same method as that for measuring the impedance slope, except that the conductive layer and surface layer present on the surface are peeled off. The impedance of the support can be measured by the same method as that for measuring the impedance before coating with the resin layer or conductive layer, or after forming the conductive member, after peeling off the conductive layer or the coating layer consisting of the resin layer and the conductive layer, etc.
[0047] <Conductive layer> As the conductive layer of the conductive member satisfying the above <first requirement> and <second requirement>, for example, a conductive layer satisfying at least one of the following configurations (i) to (iii) is preferable. Configuration (i) The volume resistivity of the matrix is 1.0×10 12 Ωcm or greater than 1.0×10 17 It must be Ωcm or less. Configuration (ii) The volume resistivity of the domain is 1.0×10 1 Ωcm or more, 1.0×10 4 Must be Ω·cm or less. Configuration (iii) The distance between adjacent domains is within the range of 0.2 μm or more and 2.0 μm or less. The distance between domains means the distance from one matrix-domain interface (also called the wall of a domain) to the shortest wall of another domain.
[0048] The above configurations (i) to (iii) will be explained below. 5 shows a partial cross-sectional view of the conductive layer in a direction perpendicular to the longitudinal direction of the conductive roller. The conductive layer has a matrix-domain structure having a matrix 6a and a domain 6b. The domain 6b contains an electronic conductive agent 6c such as carbon black. When a bias voltage is applied between the conductive support and another member to a conductive member having a conductive layer in which the domains 6b containing the electronic conductive agent 6c are dispersed in the matrix 6a, the charge is considered to move in the conductive layer as follows. That is, the charge is first accumulated in the domain near the interface with the matrix. Then, the charge is transferred in sequence from the domain located on the conductive support side to the domain located on the opposite side to the conductive support side, and reaches the surface of the conductive layer opposite to the conductive support side (hereinafter, also referred to as the "outer surface of the conductive layer"). At this time, if the charges of all the domains move to the outer surface side of the conductive layer in one charge supply step, it will take time to accumulate the charges in the conductive layer toward the next charge supply step. That is, it becomes difficult to respond to a high-speed electrophotographic image formation process. Therefore, it is preferable to prevent the transfer of charges between the domains from occurring simultaneously even when a bias voltage is applied. Also, in a high-frequency region where the movement of the charge is restricted, it is effective to accumulate a sufficient amount of charge in the domain in order to supply a sufficient amount of charge with one charge supply. As described above, in order to suppress the occurrence of simultaneous charge transfer between domains when a bias voltage is applied and to accumulate sufficient charge within the domain, it is preferable to satisfy at least one of the above configurations (i) to (iii).
[0049] <Configuration (i)> · Volume resistivity of the matrix; The volume resistivity of the matrix is 1.0×10 12 Ωcm or greater than 1.0×10 17 By setting the resistivity at Ωcm or less, it is possible to suppress the movement of electric charges in the matrix by bypassing the domains, and also to prevent the electric charges accumulated in the domains from leaking into the matrix, which would otherwise create a conductive path connecting the conductive layer. Regarding the above-mentioned <first requirement>, it is essential that charges are transferred through the domains in the conductive layer even under the application of a high-frequency bias. Therefore, the present inventors believe that a configuration in which conductive regions (domains) in which charges are sufficiently accumulated are separated by electrically insulating regions (matrix) is effective. By setting the volume resistivity of the matrix within the range of the high resistance region as described above, sufficient charges can be retained at the interface with each domain, and charge leakage from the domain can be suppressed. In addition, it was found that in order to obtain a conductive layer that satisfies the second requirement, it is effective to limit the charge transfer path to a path that passes through domains. By suppressing the leakage of charge from the domains to the matrix and limiting the charge transport path to a path that passes through multiple domains, the density of the charge present in the domains can be improved, and the amount of charge filled in each domain can be further increased. This makes it possible to increase the total number of charges that can participate in the flow of electricity on the surface of the domain as the conductive phase, which is the starting point of the flow of electricity, and as a result, it is believed that it is possible to improve the ease with which charges can be released from the surface of the conductive member.
[0050] <Method for measuring volume resistivity of matrix> The volume resistivity of the matrix can be measured, for example, by cutting a slice of a given thickness (e.g., 1 μm) containing a matrix domain structure from the conductive layer and contacting the matrix in the slice with a microprobe of a scanning probe microscope (SPM) or an atomic force microscope (AFM). For example, as shown in Fig. 7(a), the slice is cut from the elastic layer so as to include at least a part of a cross section 82a that is flat with respect to the XZ plane, where the longitudinal direction of the conductive member is the X axis, the thickness direction of the conductive layer is the Z axis, and the circumferential direction is the Y axis. Alternatively, as shown in Fig. 7(b), the slice is cut so as to include at least a part of a YZ plane (e.g., 83a, 83b, 83c) perpendicular to the axial direction of the conductive member. For example, a sharp razor, a microtome, or a focused ion beam (FIB) method may be used. To measure the volume resistivity, one side of a thin piece cut from the conductive layer is grounded. Next, a tiny probe of a scanning probe microscope (SPM) or atomic force microscope (AFM) is brought into contact with the matrix on the side of the thin piece opposite the grounded side, a DC voltage of 50V is applied for 5 seconds, and the arithmetic mean value is calculated from the ground current value measured for 5 seconds, and the applied voltage is divided by this calculated value to calculate the electrical resistance value. Finally, the resistance value is converted to volume resistivity using the film thickness of the thin piece. At this time, the SPM or AFM can measure the film thickness of the thin piece at the same time as the resistance value. The volume resistivity value of the matrix in a cylindrical charging member is determined, for example, by cutting out one thin sample from each of the regions obtained by dividing the conductive layer into four in the circumferential direction and five in the longitudinal direction, obtaining the above-mentioned measurement values, and then calculating the arithmetic average value of the volume resistivities of a total of 20 samples.
[0051] <Configuration (ii)> · Volume resistivity of the domain; The volume resistivity of the domain is 1.0×10 1 Ωcm or more 1.0×10 4 By lowering the volume resistivity of the domains, it is possible to more effectively limit the charge transport path to a path passing through a plurality of domains while suppressing unintended charge migration in the matrix. Furthermore, the volume resistivity of the domain is 1.0×10 2 It is more preferable that the volume resistivity of the domain is Ωcm or less. By lowering the volume resistivity of the domain to this range, the amount of charge moving within the domain can be dramatically improved. As a result, the impedance of the conductive layer in the low frequency range can be reduced to 1.0×10 5 It is possible to control the resistance to a lower range below Ω, and more effectively confine the charge transport path to via the domain. The volume resistivity of the domain is adjusted by using an electronic conductive agent for the rubber component of the domain to adjust the electrical conductivity to a predetermined value. As the rubber material for the domains, a rubber composition containing a rubber component for the matrix can be used. However, in order to form a matrix-domain structure, it is preferable that the difference in solubility parameter (SP value) with the rubber material forming the matrix is within the following range. That is, the difference in SP value is 0.4 (J / cm 3 ) 0.5 Above, 5.0(J / cm 3 ) 0.5 Below, especially 0.4 (J / cm 3 ) 0.5 More than 2.2(J / cm 3 ) 0.5 It is more preferable to do the following: The volume resistivity of the domain can be adjusted by appropriately selecting the type of electronic conductive agent and the amount of the electronic conductive agent added. 1 Ωcm or more 1.0×10 4 As the electronic conductive agent used to control the resistivity to Ωcm or less, an electronic conductive agent capable of greatly changing the volume resistivity from high resistance to low resistance depending on the amount dispersed is preferable. Examples of the electronic conductive agent to be mixed into the domain include carbon materials such as carbon black and graphite; conductive oxides such as titanium oxide and tin oxide; metals such as Cu and Ag; and particles that are coated with a conductive oxide or metal to make them conductive. If necessary, two or more of these electronic conductive agents may be mixed in appropriate amounts and used. Among the above-mentioned electronic conductive agents, it is preferable to use conductive carbon black, which has a high affinity with rubber and is easy to control the distance between the electronic conductive agents. The type of carbon black to be mixed into the domain is not particularly limited. Specific examples include gas furnace black, oil furnace black, thermal black, lamp black, acetylene black, and ketjen black. Among them, the DBP oil absorption of 40 cm3 is the most important factor for imparting high electrical conductivity to the domain. 3 / 100g or more 170cm 3 Conductive carbon black having a molecular weight of 100 g or less can be preferably used.
[0052] The electronic conductive agent such as conductive carbon black is preferably blended in the domain in an amount of 20 parts by mass or more and 150 parts by mass or less per 100 parts by mass of the rubber component contained in the domain. A particularly preferred blending ratio is 50 parts by mass or more and 100 parts by mass or less. Blending the electronic conductive agent in these ratios preferably contains a large amount of electronic conductive agent compared to general electrophotographic conductive members. This allows the volume resistivity of the domain to be increased to 1.0×10 1 Ωcm or more 1.0×10 4 The resistivity can be easily controlled to a range of Ωcm or less. As the conductive agent used in the domain, an ionic conductive agent may be used in combination with an electronic conductive agent. As the ionic conductive agent, for example, a quaternary ammonium salt, an imidazolium salt, a pyridinium salt, etc. can be used. As the anion of the ionic conductive agent, a perchlorate anion, a fluoroalkylsulfonylimide anion, a fluorosulfonylimide anion, a trifluoromethanesulfonate anion, a tetrafluoroborate anion, etc. can be used. At least one of these can be used. If necessary, additives that are generally used as compounding agents for rubber may be added to the rubber composition for the domains within a range that does not impair the effects of the present disclosure. Examples of such additives include fillers, processing aids, crosslinking agents, crosslinking assistants, crosslinking accelerators, antiaging agents, crosslinking accelerator assistants, crosslinking retarders, softeners, dispersants, colorants, etc.
[0053] ·Method of measuring volume resistivity of domain; The volume resistivity of the domain may be measured in the same manner as in the above <Method of measuring volume resistivity of matrix>, except that the measurement location is changed to a location corresponding to the domain, and the applied voltage during measurement of the current value is changed to 1 V. Here, it is preferable that the volume resistivity of the domain is uniform. In order to improve the uniformity of the volume resistivity of the domain, it is preferable to uniformize the amount of the electronic conductive agent in each domain. This makes it possible to more stabilize the supply of charge from the outer surface of the conductive member to the toner.
[0054] <Configuration (iii)> - Distance between adjacent domains (hereinafter also called "inter-domain distance") The arithmetic mean value Dm of the interdomain distance is preferably 0.2 μm or more and 2.0 μm or less. In order to make the conductive layer in which the domains of the volume resistivity according to the structure (ii) are dispersed in the matrix having the volume resistivity according to the structure (i) satisfy the above-mentioned <second requirement>, it is preferable that Dm is 2.0 μm or less, particularly 1.0 μm or less. On the other hand, in order to ensure that the domains are separated by the insulating region and sufficient charge is accumulated in the domains, it is preferable that Dm is 0.2 μm or more, particularly 0.3 μm or more.
[0055] · How to measure inter-domain distance; The interdomain distance can be measured as follows. First, a slice is prepared in the same manner as in the measurement of the volume resistivity of the matrix described above. In order to favorably observe the matrix domain structure, the slice may be pretreated by dyeing, deposition, or other pretreatment that favorably obtains contrast between the conductive phase and the insulating phase. The slice is then observed with a scanning electron microscope (SEM) or a transmission electron microscope (TEM) to confirm the presence of the matrix-domain structure. Among these, it is preferable to observe with an SEM at 1000 to 100,000 magnifications in terms of the accuracy of quantifying the area of the domain. The interdomain distance can be measured by quantifying the SEM image of the surface of the slice where the matrix-domain structure appears. The SE image is converted to 8-bit grayscale using image processing software (e.g., "Luzex" (trade name, manufactured by Nireco Corporation)) to obtain a monochrome image with 256 gradations. Next, the image is inverted so that the domains in the monochrome image become white, and a binary image is obtained. Next, the wall-to-wall distance of the domain size group in the binary image is calculated. The wall-to-wall distance at this time is the shortest distance between adjacent domains. In the case of a cylindrical conductive member, assuming that the length of the conductive layer in the longitudinal direction is L and the thickness of the conductive layer is T, cross sections in the thickness direction of the conductive layer as shown in FIG. 7(b) are obtained at three locations, namely, the center of the conductive layer in the longitudinal direction and L / 4 from both ends of the conductive layer toward the center. For each of the obtained cross sections, observation areas of 50 μm square are placed at any three locations in the thickness region from the outer surface of the conductive layer to a depth of 0.1T to 0.9T toward the support, and the interdomain distances observed in each of the nine observation areas may be measured. Since it is necessary to observe the surface including the outer surface of the conductive layer from the support, which is the direction of charge movement, the slices are cut in a direction that allows observation of a cross section including a normal line originating from the central axis of the support.
[0056] · Uniformity of interdomain distances; Regarding the above configuration (iii), it is more preferable that the distribution of the domain distance is uniform. The uniform distribution of the domain distance can reduce the phenomenon that the ease of discharging electric charges is suppressed when the supply of electric charges is stagnant in some places compared to the surroundings due to the localized generation of a long domain distance in the conductive layer. In the cross section where the charge is transported, that is, in the cross section in the thickness direction of the conductive layer as shown in Fig. 7(b), it is preferable that σm / Dm, where Dm is the arithmetic mean value of the interdomain distance in the observation region and σm is the variation of the interdomain distance, is 0 to 0.4. As the observation region, an observation region of 50 µm square is obtained at any three points in the thickness region from the outer surface of the conductive layer to a depth of 0.1T to 0.9T toward the support.
[0057] <How to control the domain distance> The method for controlling the inter-domain distance will be described below. Regarding the interdomain distance (1 / τ) when two immiscible polymers are melt-kneaded, Tokita has proposed a theoretical equation (7) based on Taylor’s equation (equation (4)) and Wu’s empirical equation (equations (5)-(6)). · Taylor's formula D=[C·σ / ηm·γ]·f(ηm / ηd) (4) ·Wu's Empirical Formula γ·D·ηm / σ=4(ηd / ηm)0.84·ηd / ηm>1 (5) γ·D·ηm / σ=4(ηd / ηm)-0.84·ηd / ηm<1 (6)
[0058]
number
[0059] The parameters in the formulas (4) to (7) are as follows: In equations (4) to (7), D is the domain diameter of the CMB (maximum Feret diameter Df), C is a constant, σ is the interfacial tension, ηm is the viscosity of the matrix, and ηd is the viscosity of the domain. In equation (7), γ is the shear rate, η is the viscosity of the mixture, P is the probability of collision and coalescence, φ is the domain phase volume, and EDK is the domain phase breakage energy. As shown in the above formula, the interdomain distance is mainly determined by (A) Volume ratio of the domain phase, (B) Viscosity ratio of domain to matrix, (C) shear rate, (D) Magnitude of domain phase scission energy It is possible to control it with.
[0060] Specifically, the interdomain distance can be reduced by the following method. -Reduce the interfacial tension between the domain and the matrix. -Reducing the viscosity difference between the domain and the matrix. Increase the shear rate during mixing / increase the shear energy. Increase the volume ratio of the domain phase. - Reduces the chance of collision merging.
[0061] As described above, the control of the interdomain distance proceeds simultaneously with the control of the domain size, but the interdomain distance can be controlled independently by controlling the volume ratio of the domain phases and the probability of collision and coalescence, i.e., the kneading time and shear rate. In order to efficiently transfer charges in the conductive path even under high-speed processing, it is more preferable to arrange conductive domains with uniform electrical resistance values three-dimensionally evenly and densely in the conductive layer matrix, which makes it possible to achieve a configuration having an extremely uniform conductive path without unevenness. Specifically, when the average value of the ratio of the cross-sectional area of the portion consisting of particles of the electronic conductive agent contained in each domain to the cross-sectional area of each domain appearing in a cross section in the thickness direction of the conductive layer is μ and the standard deviation of the ratio is σ, it is preferable that σ / μ is 0 or more and 0.4 or less. It is also preferable that μ is 20% or more and 40% or less. In addition to these σ and μ conditions, it is particularly preferable that at least 8 of the total 9 sample cubes having a cubic shape with one side of 9 μm sampled from any 9 points on the conductive layer satisfy the following requirement (B1).
[0062] Requirement (B1): "When one sample cube was divided into 27 unit cubes with a side length of 3 μm, and the volume Vd of the domain contained in each unit cube was calculated, Vd was 2.7 μm. 3 ~10.8μm 3 There must be at least 20 unit cubes in which
[0063] The present inventors presume the following mechanism as the factor that enables more efficient charge transfer in a conductive path in a conductive member for electrophotography even under high-speed processing: The conductive path is assumed to be an extremely uniform and even conductive path in which conductive domains with uniform electrical resistance are three-dimensionally arranged evenly and densely in a conductive layer. In a developing member that applies a bias, it is desirable to develop toners with different charge densities with a uniform charge density by performing development and discharging in the blade nip, and therefore it is necessary to keep the surface potential of the developing blade uniform for the toner size. Therefore, it is preferable that the conductive path is formed uniformly and at a high density in the thickness direction and in-plane direction from the conductive support to the surface of the developing member. When the relationship between μ and σ is such that σ / μ is 0 or more and 0.4 or less, there is no variation in the number and amount of the conductive agent portion (e.g., conductive particles) contained in each domain. As a result, the domains have uniform electrical resistance. In particular, when the relationship between μ and σ is such that σ / μ is 0 or more and 0.25 or less, the domains have even more uniform electrical resistance, which tends to enhance the effects of the present disclosure, and is therefore particularly preferred. In order to reduce σ / μ, it is preferable to increase the number and amount of conductive particle portions contained in each domain, and it is also preferable to make the domains uniform in size. Here, μ is preferably 20% or more and 40% or less. As described later, when μ is less than 20%, the amount of conductive particles is necessarily small, and the electrical connection of the conductive particles in the domain may become unstable in terms of percolation. On the other hand, when μ is more than 40%, the amount of conductive particles in the domain may increase, making it difficult to confine the conductive particles in the domain. In addition, as described later, it has been found that the effect of the present disclosure is enhanced when the filling amount of conductive particles in the domain increases, and more preferably, μ is 23% or more, and even more preferably, 28% or more.
[0064] In addition, the domains are contained in the unit cube with a side length of 3 μm at 10 to 40% by volume, and the sample cube is uniformly present throughout the conductive layer, resulting in a configuration in which the conductive domains are arranged three-dimensionally evenly and densely in the conductive layer. As will be described later, even if the total volume of the domains is increased, the proportion of the domains that are uniformly present throughout the conductive layer tends to increase. Even if the total volume of the domains is the same, the proportion of the domains that are uniformly present throughout the conductive layer tends to increase dramatically by reducing the domain size and increasing the number of domains. In other words, if the number of unit cubes each having a side length of 3 μm that satisfies the above requirement (B1) increases, the effect of the present disclosure will inevitably increase. 3 The number of unit cubes in this range is preferably 20 or more, more preferably 22 or more, and even more preferably 25 or more. In order to form a conductive path that is connected from the conductive support to the surface of the conductive layer, it is necessary to arrange the domains three-dimensionally. In other words, the connection of the conductive path from the conductive support to the surface of the conductive layer cannot be accurately constructed by only controlling the domain arrangement in a certain two-dimensional cross section. Here, "the conductive path is connected" refers to a state in which charges can move efficiently (hopping conduction, tunneling conduction, band conduction, etc.) between the domains that form the conductive path with a desired applied voltage. Although it depends on the applied voltage used, the thickness of the conductive layer, and the electrical resistance of the domain and matrix, it is particularly preferable that the distance between adjacent wall surfaces of the domains is 2.0 μm or less in a three-dimensional evaluation.
[0065] The conductive member according to this embodiment can be formed, for example, through a method including the following steps (i) to (iv). Step (i): Carbon black and Second preparing a domain-forming rubber composition (hereinafter also referred to as "CMB") comprising the rubber of the above; Step (ii): No. 1 preparing a matrix-forming rubber composition (hereinafter also referred to as "MRC") containing the rubber; Step (iii): A step of kneading the CMB and the MRC to prepare a rubber composition having a matrix-domain structure. Step (iv): A step of forming a layer of the rubber composition prepared in step (iii) directly or via another layer on a conductive support, and curing (crosslinking) the layer of the rubber composition to form the conductive layer according to the present embodiment.
[0066] The configurations (i) to (iii) can be controlled, for example, by selecting the materials used in each of the above steps and adjusting the manufacturing conditions, as will be explained below. First, regarding the configuration (i), the volume resistivity of the matrix is determined by the composition of the MRC. No. 1As the rubber, at least one of rubbers having low electrical conductivity such as natural rubber, butadiene rubber, butyl rubber, acrylonitrile butadiene rubber, urethane rubber, silicone rubber, fluororubber, isoprene rubber, chloroprene rubber, styrene-butadiene rubber, ethylene-propylene rubber, and polynorbornene rubber can be used. In addition, on the premise that the volume resistivity of the matrix can be set within the above range, a filler, a processing aid, a crosslinking agent, a crosslinking aid, a crosslinking accelerator, a crosslinking accelerator aid, a crosslinking retarder, an antiaging agent, a softener, a dispersant, and a colorant may be added to the MRC as necessary. On the other hand, in order to set the volume resistivity of the matrix within the above range, it is preferable that the MRC does not contain an electronic conductive agent such as carbon black.
[0067] The structure (ii) can be adjusted by adjusting the amount of the electronic conductive agent in the CMB. For example, the electronic conductive agent may be a DBP having an oil absorption of 40 cm 3 / 100g or more, 170cm 3 Take the case of using conductive carbon black having a carbon black content of 40% by mass or more and 200% by mass or less of conductive carbon black based on the total mass of the CMB as an example.
[0068] Furthermore, with regard to the configuration (iii), it is effective to control the following four items (a) to (d). (a) Difference in interfacial tension σ between CMB and MRC (b) Ratio of the viscosity of the CMB (ηd) and the viscosity of the MRC (ηm) (ηm / ηd) (c) Shear rate (γ) and energy amount (EDK) during kneading of CMB and MRC in step (iii) (d) Volume fraction of CMB relative to MRC in step (iii)
[0069] (a) Interfacial tension difference between CMB and MRC Generally, when two incompatible rubbers are mixed, phase separation occurs. This is because the interactions between the same polymers are stronger than those between different polymers, so the same polymers aggregate together to lower the free energy and stabilize. The interface of the phase-separated structure comes into contact with different polymers, so the free energy is higher than the interior, which is stabilized by the interactions between the same molecules. As a result, interfacial tension occurs, which tries to reduce the area of contact between different polymers in order to reduce the free energy of the interface. When this interfacial tension is small, the different polymers tend to mix more uniformly in order to increase entropy. The state of uniform mixing is called dissolution, and there is a tendency for the SP value (solubility parameter), which is an indicator of solubility, to correlate with interfacial tension. In other words, the interfacial tension difference between the CMB and the MRC is considered to correlate with the SP value difference of the rubber contained in each. For the first rubber in the MRC and the second rubber in the CMB, it is preferable to select rubbers whose absolute value difference in solubility parameters falls within the following range. Preferably, it is 0.4 (J / cm 3 ) 0.5 Above, 5.0(J / cm 3 ) 0.5 Below, especially 0.4 (J / cm 3 ) 0.5 More than 2.2(J / cm 3 ) 0.5 Within this range, a stable phase separation structure can be formed, and the domain diameter D of the CMB can be reduced. Here, we consider the CMB Second Specific examples of the rubber include the following rubber materials: natural rubber (NR), isoprene rubber (IR), butadiene rubber (BR), styrene-butadiene rubber (SBR), butyl rubber (IIR), ethylene-propylene rubber (EPM, EPDM), Chloroprene Rubber (CR), nitrile rubber (NBR), hydrogenated nitrile rubber (H-NBR), silicone rubber, and urethane rubber (U). At least one of these can be used. The thickness of the conductive layer is not particularly limited as long as the functions and effects of the intended conductive member can be obtained. The thickness of the conductive layer is preferably at least 100 μm (0.1 mm) or more, particularly preferably 0.3 mm or more, and even more preferably 1.0 mm or more. Also, it is preferably 4.5 mm or less.
[0070] <Method for Measuring SP Value> The SP value can be accurately calculated by creating a calibration curve using a material with a known SP value. As this known SP value, the catalog value of the material manufacturer can also be used. For example, for NBR and SBR, regardless of the molecular weight, the SP value is almost determined by the content ratio of acrylonitrile or styrene. Therefore, the rubbers constituting the matrix and the domain are analyzed for the content ratio of acrylonitrile or styrene using analytical methods such as pyrolysis gas chromatography (Py-GC) and solid NMR. Then, the SP value can be calculated based on the content ratio from the calibration curve obtained from a material with a known SP value. Also, for isoprene rubber, the SP value is determined by the isomeric structure such as 1,2-polyisoprene, 1,3-polyisoprene, 3,4-polyisoprene, cis-1,4-polyisoprene, and trans-1,4-polyisoprene. Therefore, similar to SBR and NBR, the isomer content ratio is analyzed by Py-GC and solid NMR, etc., and the SP value can be calculated from a material with a known SP value.
[0071] (b) Viscosity Ratio between CMB and MRC The closer the viscosity ratio (ηd / ηm) between CMB and MRC is to 1, the smaller the maximum Feret diameter of the domains can be. Specifically, the viscosity ratio is preferably 1.0 or more and 2.0 or less. The viscosity ratio between CMB and MRC can be adjusted by selecting the Mooney viscosity of the raw rubber used for CMB and MRC, and by mixing the type and amount of filler. It can also be adjusted by adding a plasticizer such as paraffin oil to an extent that does not interfere with the formation of a phase separation structure. The viscosity ratio can also be adjusted by adjusting the temperature during kneading. The viscosity of CMB and MRC can be obtained by measuring the Mooney viscosity ML (1+4) at the rubber temperature during kneading based on JIS K6300-1:2013.
[0072] (c) Shear rate and energy during mixing of MRC and CMB The faster the shear rate during kneading of MRC and CMB, and the greater the amount of energy during shearing, the smaller the interdomain distance can be. The shear rate can be increased by increasing the inner diameter of the stirring member such as the blade or screw of the kneader, decreasing the gap between the end face of the stirring member and the inner wall of the kneader, or increasing the rotation speed. In order to increase the energy during shearing, the rotation speed of the stirring member can be increased, MRC In No. 1 Rubber and CMB The first 2 This can be achieved by increasing the viscosity of the rubber.
[0073] (d) Volume fraction of CMB relative to MRC The volume fraction of the CMB relative to the MRC correlates with the probability of the CMB colliding with the MRC. Specifically, when the volume fraction of the CMB relative to the MRC is reduced, the probability of the CMB and MRC colliding with each other decreases. In other words, the interdomain distance can be reduced by reducing the volume fraction of the domains in the matrix within a range that provides the required electrical conductivity. The volume fraction of the CMB relative to the MRC is preferably 15% or more and 40% or less.
[0074] <Domain shape> The shape of the domain is preferably close to a circle. The ratio of the area of the domain to the area of the circle equivalent to the maximum Feret diameter of the domain is preferably 0.6 or more and 1 or less. The maximum value of this ratio is 1, and a state where it is 1 indicates that the domain is a perfect circle. If these ratios are smaller than 0.6, the shape of the domain will have anisotropy, that is, anisotropy of the electric field will be expressed. As a result, an electric field concentration point will be formed, and the transport of charges will be concentrated, so that a current with a long duration is likely to occur. The closer these ratios are to 1, the more the electric field concentration will be suppressed, and the less likely fog images will occur. The maximum Feret diameter is the value when the periphery of the observed domain is sandwiched between two parallel lines and the length is the longest when the two parallel lines are connected by a perpendicular line. The circle equivalent to the maximum Feret diameter is a circle whose diameter is the maximum Feret diameter.
[0075] <Method of measuring domain area S1 and maximum Feret diameter circle area S2> The shape of the domain can be quantified using an image obtained by creating and observing a cross section in the same manner as the above-mentioned method for measuring the domain size and the distance between domains. Specifically, after binarizing the cross section in the same manner as the above-mentioned method for measuring the domain size, the domain area and maximum Feret diameter are calculated for each domain in the image using image processing software. Next, the ratio of the actual domain area S1 to the area S2 of the circle equivalent to the maximum Feret diameter obtained from the maximum Feret diameter can be calculated. In measuring S1 and S2, the developing member is divided equally, preferably into 20 sections, and one thin sample is cut from each of the sections. After obtaining the above-mentioned measurements, the arithmetic average values of S1 and S2 for a total of 20 samples are taken as the measured values of S1 and S2. In the case of a cylindrical developing member, the cylindrical member is divided into four regions in the circumferential direction and five regions in the longitudinal direction, and one thin sample is cut out from each of these regions. After obtaining the above-mentioned measurements, the arithmetic average values of S1 and S2 for a total of 20 samples are taken as the measured values of S1 and S2.
[0076] In order to suppress resistance fluctuation and electric field concentration due to aggregation of the electronic conductive agent and to more efficiently achieve the effects of the present disclosure, the conductive layer preferably satisfies the following requirements. That is, when the longitudinal length of the conductive layer is L, attention is paid to cross sections in the thickness direction of the conductive layer at three locations: the longitudinal center of the conductive layer, and L / 4 from both ends of the conductive layer toward the center. When the thickness of the conductive layer is T, observation regions of 15 μm square are placed at any three locations in a thickness region from the outer surface of the conductive layer to a depth of 0.1T to 0.9T for each of the cross sections. It is preferable that 80% or more by number of domains observed in each of the nine observation regions satisfy the following requirements (B2) and (B3).
[0077] Requirements (B2) The ratio of the cross-sectional area of the conductive particles contained in the domain to the cross-sectional area of the domain is 20% or more. Requirement (B3) When the perimeter of a domain is A and the envelope perimeter of the domain is B, A / B is 1.00 or more and 1.10 or less.
[0078] The above requirements (B2) and (B3) can be said to be regulations related to the shape of the domain. The "shape of the domain" is defined as the cross-sectional shape of the domain that appears in a cross section in the thickness direction of the conductive layer. In the case of a cylindrical conductive member, when the length of the conductive layer in the longitudinal direction is L and the thickness of the conductive layer is T, cross sections in the thickness direction of the conductive layer as shown in FIG. 7(b) are obtained at three locations, namely, the center of the conductive layer in the longitudinal direction and L / 4 from both ends of the conductive layer toward the center. For each of the obtained cross sections, observation areas of 15 μm square are placed at any three locations in the thickness region from the outer surface of the conductive layer to a depth of 0.1T to 0.9T toward the support. The domain shape is defined by the shape of each domain observed in each of the nine observation areas. The domains are preferably shaped so that there are no irregularities on their periphery. By reducing the number of irregularities in the shape, the non-uniformity of the electric field between the domains can be reduced, that is, the number of places where the electric field concentrates can be reduced, and the phenomenon of excessive charge transport in the matrix can be reduced. The present inventors have found that the amount of electronic conductive agent (conductive particles) contained in one domain affects the external shape of the domain. That is, the more the amount of conductive particles filled in one domain increases, the more the shape of the domain becomes closer to a sphere. The more domains that are close to a sphere, the fewer the points of concentration of electron transfer between domains can be. And, according to the study by the present inventors, although the reason is not clear, a domain in which the ratio of the total cross-sectional area of the conductive particles observed in the cross section is 20% or more based on the cross-sectional area of one domain can have a shape closer to a sphere. As a result, it is preferable because it can have an external shape that can significantly alleviate the concentration of electron transfer between domains. Specifically, it is preferable that the ratio of the cross-sectional area of the conductive particles contained in the domain to the cross-sectional area of the domain is 20% or more.
[0079] The present inventors have found that it is preferable for the domain to have a shape with no irregularities on its peripheral surface to satisfy the following formula (8). 1.00≦A / B≦1.10 (8) (A: domain perimeter, B: domain envelope perimeter)
[0080] Equation (8) shows the ratio between the perimeter A of the domain and the envelope perimeter B of the domain. Here, the envelope perimeter is the length of the convex envelope 73 of the domain 71 observed in the observation area, as shown in Fig. 6. Note that the convex envelope is the smallest convex set that includes all points in the domain 71. The ratio of the domain perimeter to the domain envelope perimeter has a minimum value of 1, which indicates that the domain has a cross-sectional shape with no concaves, such as a perfect circle or ellipse. If this ratio exceeds 1.1, the domain will have large concaves and convexes, which means that anisotropy of the electric field will appear.
[0081] As defined in requirement (B2), by densely packing conductive particles into a domain, the external shape of the domain can be made closer to a sphere, and unevenness can be made small, as defined in requirement (B3). In order to obtain a domain in which conductive particles are densely packed as specified in requirement (B2), the conductive particles should have a DBP oil absorption of 40 cm 3 / 100g or more 80cm 3 Carbon black having a DBP oil absorption (cm) of 100 g or less can be particularly preferably used. 3 / 100g) is the volume of dibutyl phthalate (DBP) that can be adsorbed by 100g of carbon black, and is measured in accordance with Japan Industrial Standards (JIS) K 6217-4:2017 (Carbon black for rubber - Basic properties - Part 4: Determination of oil absorption (including compressed samples)). Generally, carbon black has a cluster-like higher-order structure in which primary particles with an average particle size of 10 nm to 50 nm are aggregated. This cluster-like higher-order structure is called structure, and its degree is measured by the DBP oil absorption (cm). 3 / 100g).
[0082] Generally, carbon black with a developed structure has a high reinforcing effect on rubber, which makes it difficult to incorporate the carbon black into rubber and increases the shear torque during kneading, making it difficult to increase the amount of carbon black loaded into the domain. On the other hand, conductive carbon black with DBP absorption within the above range has an underdeveloped structure, so carbon black aggregates less and disperses well in rubber, allowing a larger amount of carbon black to be filled into the domain, which in turn makes it easier to obtain a domain with an outer shape closer to a sphere. Furthermore, carbon black with a developed structure tends to aggregate easily, and the aggregates tend to form lumps with large uneven structures. If such aggregates are contained in a domain, it is difficult to obtain the domain related to requirement (B3). This may even affect the shape and form an uneven structure. On the other hand, conductive carbon black with a DBP oil absorption within the above range is effective in creating the domain related to requirement (B3) because it is difficult to form aggregates.
[0083] <Method of measuring each parameter related to domain shape> First, a slice is prepared in the same manner as in the measurement of the volume resistivity of the matrix described above. However, as described below, the slice is prepared by a cross section perpendicular to the longitudinal direction of the conductive member, and the shape of the domain is evaluated on the plane of the slice corresponding to the cross section in the thickness direction of the conductive layer. The reason for this will be described below. 7 shows a diagram illustrating the shape of conductive member 81 in three dimensions along three axes, specifically, X, Y, and Z. In Fig. 7, the X-axis indicates a direction parallel to the longitudinal direction (axial direction) of the conductive member, and the Y-axis and Z-axis indicate directions perpendicular to the axial direction of the conductive member. FIG. 7(a) shows an image of a conductive member cut out at a cross section 82a parallel to an XZ plane 82. The XZ plane can rotate 360° around the axis of the conductive member. Considering that the conductive member rotates while in contact with the toner on its surface and supplies a charge to the toner, the cross section 82a parallel to the XZ plane 82 indicates a surface where a charge is simultaneously supplied at a certain timing. A surface equivalent to a certain amount of the cross section 82a passes through, whereby a charge is supplied to the toner. Therefore, in order to evaluate the shape of the domain, which correlates with the electric field concentration in the conductive member, it is necessary to evaluate a cross section parallel to the YZ plane 83 shown in Fig. 7(b) perpendicular to the axial direction of the conductive member, which allows evaluation of the domain shape including a certain amount of cross section 82a, rather than analyzing a cross section where charge supply occurs at the same time at a certain moment, such as cross section 82a. For this evaluation, when the length in the longitudinal direction of the conductive layer is L, a total of three cross sections are selected: cross section 83b at the center in the longitudinal direction of the conductive layer, and two cross sections (83a and 83c) at L / 4 from both ends of the conductive layer toward the center. Regarding the observation positions of the cross sections 83a to 83c, when the thickness of the conductive layer is T, observation areas of 15 μm square are placed at any three locations in the thickness region from the outer surface of each slice to a depth of 0.1T or more and 0.9T or less, and measurements are taken at a total of nine observation areas. The cross section can be formed by freeze fracturing, cross polishing, focused ion beam (FIB), or other methods. In consideration of the smoothness of the cross section and pretreatment for observation, the FIB method is preferred. In order to favorably observe the matrix domain structure, pretreatment such as dyeing or deposition may be performed to favorably obtain contrast between the conductive phase and the insulating phase. The obtained slice can be observed using a scanning electron microscope (SEM) or a transmission electron microscope (TEM) to observe the matrix domain structure in the conductive layer. Specifically, for example, it is preferable to obtain an SEM image at a magnification of 1000 to 100,000 times in terms of accuracy in quantifying the area of the domain. The parameters related to the domains can be measured by quantifying the SEM image. That is, the SEM image is converted to 8-bit grayscale using image processing software such as "ImageProPlus" (product name, manufactured by Media Cybernetics) to obtain a monochrome image with 256 gradations. Next, the black and white of the image are inverted so that the domains in the monochrome image become white, and a binarization threshold is set for the brightness distribution of the image based on the algorithm of Otsu's discriminant analysis method to obtain a binary image. Next, when the thickness of the conductive layer in the binary image is T, observation areas of 15 μm square are placed at any three positions in the area corresponding to the thickness area from the outer surface of the conductive layer to a depth of 0.1T to 0.9T. Then, the parameters related to the domains in each observation area are measured using the count function of the image processing software.
[0084] <Method for measuring the cross-sectional area ratio μ of electronic conductive material in a domain> The cross-sectional area ratio of the electronic conductive agent in the domain is calculated for each domain in the observation region by using the counting function of the image processing software to calculate the cross-sectional area S of the domain and the sum Sc of the cross-sectional area of the part consisting of the conductive agent in each domain, and then the arithmetic average value μ (%) of Sc / S is calculated.
[0085] <Method of measuring domain perimeter A and envelope perimeter B> The domain perimeter and envelope perimeter are calculated for each domain in the observation area using the counting function of the image processing software, to calculate the perimeter A and domain envelope perimeter B, and to calculate the arithmetic mean of the domain perimeter ratio A / B.
[0086] <Domain size> In the domains according to this embodiment, the average of the maximum Feret diameters (hereinafter also simply referred to as "domain diameters") L of the domains contained in each of the domains satisfying the above-mentioned configurations (iv) and (v) is preferably 0.1 μm or more and 5.0 μm or less. By setting the average value of the domain diameter L to 0.1 μm or more, the path along which the charge moves in the conductive layer can be more effectively limited to the desired path. Furthermore, by setting the average value of the domain diameter L to 5.0 μm or less, the ratio of the surface area to the total volume of the domain, i.e., the specific surface area, can be exponentially increased, and the efficiency of discharging the charge from the domain can be dramatically improved. For the above reasons, the average value of the domain diameter L is preferably set to 2.0 μm or less, and more preferably 1.0 μm or less. In order to further reduce the electric field concentration between the domains, it is preferable to make the outer shape of the domain closer to a sphere. To achieve this, it is preferable to make the domain diameter smaller within the above-mentioned range. As a method for this, for example, a method of controlling the domain diameter of CMB to be smaller in a process of preparing a rubber mixture in which MRC and CMB are mixed and phase-separated to form a CMB domain in an MRC matrix can be mentioned. By reducing the domain diameter of CMB, the specific surface area of CMB increases, and the interface with the matrix increases, so that a tension that tries to reduce the tension acts on the interface of the CMB domain. As a result, the outer shape of the CMB domain becomes closer to a sphere.
[0087] In relation to the above-mentioned configuration (iii), in order to make the domain distance uniform, it is effective to make the domain sands small according to the above-mentioned formulas (4) to (7). Furthermore, the matrix domain structure is also governed by where the kneading process is stopped in the process in which the raw rubber of the domain is split and the particle size gradually becomes smaller. Therefore, the uniformity of the domain distance can be controlled by the kneading time in the kneading process and the kneading rotation speed, which is an index of the intensity of the kneading, and the longer the kneading time and the higher the kneading rotation speed, the more the uniformity of the domain distance can be improved.
[0088] · Uniformity of domain size; The more uniform the domain size, that is, the narrower the particle size distribution, the better. By making the distribution of the size of the domains through which the charge passes in the conductive layer uniform, the concentration of the charge in the matrix domain structure can be suppressed, and the ease of the charge being released can be effectively increased over the entire surface of the conductive member. As for the uniformity of the domain size, it is preferable that the ratio σd / D of the standard deviation σd of the domain size and the average value D of the domain size is 0 or more and 0.4 or less. The domain size is obtained from an observation area of 50 μm square at any three points in the thickness region from the outer surface of the conductive layer to a depth of 0.1T to 0.9T toward the support in the cross section where the charge is transported, that is, in the cross section in the thickness direction of the conductive layer.
[0089] In order to improve the uniformity of the domain size, the method is the same as the method for improving the uniformity of the interdomain distance described above, and the uniformity of the domain size is improved by reducing the domain size according to formulas (4) to (7). Furthermore, the matrix domain structure is also governed by where the kneading process is stopped in the process in which the raw rubber of the domain is split and the particle size gradually becomes smaller. Therefore, the uniformity of the domain size can be controlled by the kneading time in the kneading process and the kneading rotation speed, which is an index of the intensity of the kneading, and the longer the kneading time and the higher the kneading rotation speed, the more the uniformity of the domain size can be improved.
[0090] <How to check the matrix-domain structure> The presence of a matrix-domain structure in the conductive layer can be confirmed by preparing a thin slice from the conductive layer and closely observing the cross section formed in the thin slice. Examples of the means for thinning include a sharp razor, a microtome, FIB, etc. In order to observe the matrix-domain structure more accurately, the thin section for observation may be subjected to a pretreatment such as a staining treatment or a deposition treatment, which can favorably obtain a contrast between the domain as a conductive phase and the matrix as an insulating phase. The cross section of the formed and optionally pretreated thin piece can be observed with a laser microscope, a scanning electron microscope (SEM) or a transmission electron microscope (TEM) to confirm the presence of the matrix-domain structure. Observation with a scanning electron microscope (SEM) is preferable as a method for easily and accurately confirming the matrix-domain structure. A thin piece of the conductive layer is obtained by the above-mentioned method, and an image is obtained by observing the surface of the thin piece at 1000 to 10000 times magnification. Then, using image processing software such as "ImageProPlus" (product name: manufactured by Media Cybernetics), an 8-bit grayscale image is obtained to obtain a monochrome image with 256 gradations. Next, the black and white of the image are inverted so that the domains in the cross section become white, and the image is binarized to obtain an analysis image. The presence or absence of a matrix-domain structure can be determined from the analysis image that has been image-processed to a state in which the domains and matrix are distinguished by binarization. Specifically, for example, when a structure in which a plurality of domains exist in an isolated state in a matrix can be confirmed in the analysis image, as shown in Fig. 5, it can be determined that a matrix-domain structure exists in the conductive layer. The existence of domains in an isolated state in a matrix can mean, for example, a state in which each domain is not connected to other domains, the matrix is connected in the image, and the domains are divided by the matrix. The above-mentioned confirmation can be carried out by dividing the conductive layer of the conductive member into 5 equal parts in the longitudinal direction and 4 equal parts in the circumferential direction, and randomly selecting one section from each area, for a total of 20 sections, and then performing the above-mentioned measurements.
[0091] In this embodiment, when used as a developing member, the surface layer has a volume resistivity of 1.0×10 4 ~1.0×10 15 It is characterized by a resistivity of Ωcm. The surface layer has the function of imparting triboelectricity to the toner, protecting the surface of the developing member, and suppressing wear and damage to the surface of the developing member. The volume resistivity of the surface layer can be adjusted by adding an electronic conductive agent or an ionic conductive agent to the resin component that serves as the binder. The binder resin functions as a carrier for the electronic conductive agent, the ionic conductive agent, the filler, and the additives.
[0092] As the binder resin component, known resins can be used, and although there are no particular limitations, examples thereof include the following, and one or a combination of two or more of these can be used. Specific examples of the resin include polyurethane resin, polyester resin, polyether resin, acrylic resin, epoxy resin, amino resin such as melamine, amide resin, imide resin, amide-imide resin, phenol resin, vinyl resin, silicone resin, fluorine resin, polyalkyleneimine resin, polycarbonate resin, and the like.
[0093] Polyurethane resins are particularly preferred from the viewpoints of film strength and toner charging properties, and among them, thermosetting polyether polyurethane resins, polyester polyurethane resins, and polycarbonate resins are preferably used because they also have flexibility. These thermosetting polyurethane resins are obtained by reacting a known polyether polyol, polyester polyol, or polycarbonate polyol with an isocyanate compound.
[0094] Examples of polyether polyols include polyethylene glycol, polypropylene glycol, and polytetramethylene glycol. Examples of polyester polyols include the following: polyester polyols obtained by condensation reaction of a diol component such as ethylene glycol, 1,2-propanediol, 1,4-butanediol, 1,6-hexanediol, 3-methyl-1,4-pentanediol, or neopentyl glycol, or a triol component such as trimethylolpropane, with a dicarboxylic acid such as succinic acid, adipic acid, phthalic anhydride, terephthalic acid, or hexahydroxyphthalic acid. Examples of polycarbonate polyols include the following: Polycarbonate polyols obtained by a condensation reaction between a diol component such as 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 2-methyl-1,8-octanediol, 3-methyl-1,5-pentanediol, diethylene glycol, polyethylene glycol, polypropylene glycol, or polytetramethylene glycol, and a dialkyl carbonate such as phosgene or dimethyl carbonate, or a cyclic carbonate such as ethylene carbonate.
[0095] If necessary, these polyol components may be chain-extended in advance with an isocyanate such as 2,4-tolylene diisocyanate (TDI), 1,4-diphenylmethane diisocyanate (MDI), or isophorone diisocyanate (IPDI) to form a prepolymer. The isocyanate compound to be reacted with these polyol components is not particularly limited, and examples of the isocyanate compound that can be used include aliphatic polyisocyanates such as ethylene diisocyanate and 1,6-hexamethylene diisocyanate (HDI), alicyclic polyisocyanates such as isophorone diisocyanate (IPDI), cyclohexane 1,3-diisocyanate and cyclohexane 1,4-diisocyanate, aromatic isocyanates such as 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate (TDI), 4,4'-diphenylmethane diisocyanate (MDI), polymeric diphenylmethane diisocyanate, xylylene diisocyanate and naphthalene diisocyanate, as well as copolymers, isocyanurates, TMP adducts, biuret forms and blocks thereof. Among these, aromatic isocyanates such as tolylene diisocyanate, diphenylmethane diisocyanate, and polymeric diphenylmethane diisocyanate are more preferably used. The mixing ratio of the isocyanate compound to be reacted with the polyol component is preferably in the range of 1.0 to 2.0 such that the ratio of isocyanate groups to hydroxyl groups is 1.0, since this makes it possible to suppress the remaining of unreacted components.
[0096] When a urethane resin is used as the binder resin of the surface layer, the urethane group concentration is preferably 1.5% or more and 6.5% or less. When the urethane group concentration is 1.5% or more, the film strength of the surface layer is high due to the interaction between the urethane groups, which is preferable from the viewpoint of durability. Also, when the urethane group concentration is 6.5% or less, there are few excess urethane groups that become affinity sites for water molecules. Therefore, when used alternately in high temperature and high humidity environments and low temperature and low humidity environments, the surface layer is less likely to expand or contract. As a result, even when used in harsh environments, the occurrence of microcracks at the interface between the surface layer of the conductive member and the conductive layer can be suppressed, and durability can be further improved.
[0097] Furthermore, it is particularly preferable that the surface layer 4 contains a urethane resin having any of the structures of the structural formulas (1) to (3), since this provides a further improvement in durability even when used in harsh environments.
[0098] [ka] In structural formulas (1) to (3), R 1 ~R 3 each independently represents a linear or branched divalent hydrocarbon group having 4 to 8 carbon atoms.
[0099] Specifically, the structures of structural formulas (1) to (3) respectively represent ether structures, ester structures, and carbonate structures with a large number of carbon atoms. Resins containing these structures have a large number of carbon atoms, so they contain fewer ether bonds, ester bonds, and carbonate bonds per unit weight. As a result, the affinity with water molecules in the resin decreases, and the moisture content can be kept low even in a high-temperature, high-humidity environment. In particular, it is preferable to react the structural formulas (1) to (3) as polyols with an isocyanate compound to obtain a desired urethane resin. As a result, even when the film is used alternately in high temperature and high humidity environments and low temperature and low humidity environments, the expansion and contraction of the surface layer can be suppressed, providing even greater durability even when used in harsh environments.
[0100] Examples of polyols having the structure of structural formula (1) include polytetramethylene glycol, polyhexamethylene glycol, polyoctamethylene glycol, and ring-opening copolymer polyols of tetrahydrofuran and 3-methyltetrahydrofuran.
[0101] Examples of the polyol having the structure of structural formula (2) include: Examples of the polyester polyols include polyester polyols obtained by a condensation reaction between a diol component such as 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 3-methyl-1,4-pentanediol, or neopentyl glycol, or a triol component such as trimethylolpropane, and a dicarboxylic acid such as adipic acid, pimelic acid, suberic acid, azelaic acid, or sebacic acid.
[0102] Examples of the polyol having the structure of structural formula (3) include: Examples of the polycarbonate polyol include polycarbonate polyols obtained by a condensation reaction between a diol component such as 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 3-methyl-1,4-pentanediol, or neopentyl glycol and a dialkyl carbonate such as phosgene or dimethyl carbonate.
[0103] In addition to the thermal curing reaction using an isocyanate compound, a compound having a vinyl group or an acroyl group introduced at the end instead of the polyol can be cured with ultraviolet light or an electron beam. In a curing system using ultraviolet light or an electron beam, the curing reaction can be completed in a shorter time than in a curing system using an isocyanate.
[0104] In order to impart electrical conductivity to the surface layer, an electronic conductive agent is appropriately blended. As the electronic conductive agent, conductive carbon black; conductive metals such as aluminum and copper; and fine particles of conductive metal oxides such as tin oxide and titanium oxide can be used. Among these, carbon black is preferred because it is relatively easy to obtain and provides good electrical conductivity. When carbon black is used as the electronic conductive agent, it is preferred to blend 2 to 50 parts by mass of carbon black with respect to 100 parts by mass of the binder resin.
[0105] An ionic conductive agent may be used as the conductive agent, and may be used in combination with the electronic conductive agent. As the ionic conductive agent, for example, a quaternary ammonium salt, an imidazolium salt, a pyridinium salt, a sulfonium salt, a phosphonium salt, etc. can be used. As the anion of the ionic conductive agent, a perchlorate anion, a fluoroalkylsulfonylimide anion, a fluorosulfonylimide anion, a trifluoromethanesulfonate anion, a tetrafluoroborate anion, a hexafluorophosphate anion, a dicyanamide anion, a thiocyanate anion, a dicyanosulfonylimide anion, etc. At least one of these can be used.
[0106] The surface layer may contain a non-conductive filler such as silica, quartz powder, titanium oxide, zinc oxide or calcium carbonate, if necessary. When a method of coating a paint is used to form the surface layer, a non-conductive filler can be added to act as a film-forming aid. The content of the non-conductive filler is preferably 10% by mass or more and 30% by mass or less relative to 100 parts by mass of the resin components forming the surface layer, i.e., the combined components of the binder resin and the resin having the structure represented by structural formula (1).
[0107] The conductive member may have an appropriate surface roughness as required. When the conductive member is a developing roller or a developing sleeve, the surface roughness is preferably in the range of 2.0 to 10.0 μm in ten-point average roughness (Rz), and more preferably in the range of 2.0 to 4.5 μm. When the conductive member is a developing blade, the surface roughness is preferably in the range of 0.0 to 6.0 μm in ten-point average roughness (Rz), and more preferably in the range of 0.0 to 1.5 μm. When the surface roughness is in this range, both uniform contact with the toner and an appropriate amount of toner transport are achieved, and it is easy to uniformly supply charge to the toner. Methods for forming the surface roughness of the conductive member include adding fine particles to the surface layer, polishing, mold transfer, and laser treatment. When fine particles are added for controlling the roughness, the fine particles preferably have a volume average particle size of 3 to 20 μm. Furthermore, the amount of particles added to the surface layer 4 is preferably 1 to 50 parts by mass per 100 parts by mass of the resin solid content of the surface layer 4. As the fine particles for controlling the roughness, fine particles of polyurethane resin, polyester resin, polyether resin, polyamide resin, acrylic resin, and phenol resin can be used.
[0108] When the conductive member is in the form of a roller, the conductive layer can be formed by molding a liquid rubber material or by extrusion molding a kneaded rubber material. When the conductive member is in the shape of a blade, the molding method includes molding, injection molding, extrusion molding, and centrifugal molding.
[0109] The method for forming the surface layer is not particularly limited, and examples thereof include spraying, dipping, or roll coating with a paint. The dip coating method in which the paint is allowed to overflow from the upper end of a dipping tank as described in JP-A-57-5047 is a simple method for forming the surface layer and has excellent production stability.
[0110] When the conductive member according to this embodiment is used as a charging member, it is also effective in that the charge is uniformly applied to the toner and external additives. When toner or external additives adhere to a charging member, negative / positive charges of the same sign can be gradually applied to the toner from the outer surface due to the negative / positive bias voltage applied to the charging member. This negative / positive charge is supplied from the conductive support, transported to the charging member surface, and then reaches the dirt. When sufficient charges are accumulated on the dirt, an electrostatic force acts in the electric field formed from the charging member surface toward the photosensitive drum, and exceeds the adhesive force between the member surface and the dirt, causing a "discharge" phenomenon in which the dirt peels off from the member surface and moves to the photosensitive drum side. When a conventional charging member is applied to a high-speed process in a harsh environment, the charge cannot be sufficiently supplied to the dirt, and discharge is suppressed, resulting in dirt accumulation on the charging member and image defects such as the associated white spots. On the other hand, in the present embodiment, charge transport to the charging member surface is efficiently performed, and sufficient charge can be supplied to the dirt, so discharge can be performed sufficiently, and the accumulation of dirt on the member and the occurrence of white spots are suppressed.
[0111] Hereinafter, the electronic conductive agent, binder resin, universal hardness of the surface layer, surface layer convex portions derived from the electronic conductive agent, roughening particles, other additives, and layer thickness of the surface layer that are preferable when the conductive member of this embodiment is used as a charging member will be described in this order.
[0112] <Electronic conductive agent> The surface layer preferably contains carbon black as an electronic conductive agent. The fast response of the electronic conductive agent enables uniform charge supply to the toner even in a high-speed process. The electronic conductive agent can be the electronic conductive agent (conductive particles) described above. These conductive particles can be used alone or in combination of two or more. In addition, composite particles in which silica particles are coated with conductive particles can also be used as the conductive particles. Carbon black is preferable as the conductive particles used in the surface layer. Since carbon black has a low specific gravity and high conductivity, it is easy to control the conductivity imparted to the surface layer by adjusting the amount added to the binder resin. Furthermore, this embodiment is preferable because it is necessary to keep the hardness of the surface layer low.
[0113] <Binder resin> As the binder resin, known binder resins can be used. For example, resins, natural rubber, vulcanized natural rubber, synthetic rubber, and other rubbers can be used. As the resin, fluororesin, polyamide resin, acrylic resin, polyurethane resin, silicone resin, butyral resin, styrene-ethylene-butylene-olefin copolymer, olefin-ethylene-butylene-olefin copolymer, and the like can be used. In addition, as the binder resin, it is preferable that it does not contain an ether bond such as polyethylene oxide or polypropylene oxide. Although ether-based urethane resins can reduce the universal hardness, the volume resistivity of the resin decreases, so that it may not be suitable as the binder resin of this embodiment. The binder resins can be used alone or in combination of two or more kinds. Among these, as the binder resin, in order to achieve both flexibility by reducing the universal hardness of the surface layer and high resistance of the surface layer, it is particularly preferable that the binder resin is a resin containing a carbonate structure. Since the carbonate structure has low polarity, the volume resistivity of the binder resin itself can be maintained high. Specifically, polycarbonate-based polyurethane obtained by copolymerizing polycarbonate polyol and polyisocyanate is preferred.
[0114] Examples of polycarbonate polyols include polynonamethylene carbonate diol, poly(2-methyl-octamethylene) carbonate diol, polyhexamethylene carbonate diol, polypentamethylene carbonate diol, poly(3-methylpentamethylene) carbonate diol, polytetramethylene carbonate diol, polytrimethylene carbonate diol, poly(1,4-cyclohexanedimethylene carbonate) diol, poly(2-ethyl-2-butyl-trimethylene) carbonate diol, and random / block copolymers thereof.
[0115] The polyisocyanate is selected from commonly used known ones, for example, toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), polymeric diphenylmethane polyisocyanate, hydrogenated MDI, xylylene diisocyanate (XDI), hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), etc. Among these, aromatic isocyanates such as toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), and polymeric diphenylmethane polyisocyanate are more preferably used.
[0116] <Universal hardness of surface layer> In order to suppress the generation of contaminants, it is effective to prevent the toner from cracking or deforming. For this purpose, it is preferable that the surface layer is flexible. The hardness of the conductive member according to the present disclosure is 1.0 N / mm for the "universal hardness (at t=1 μm)" at a depth of 1 μm from the surface of the surface layer. 2 More than 7.0N / mm 2 Since the size of the external additives and toner is on the order of submicrons to several microns, it is preferable to control the hardness in the immediate vicinity of the outer surface, which is the surface of the surface layer that comes into contact with the external additives and toner. Specifically, the universal hardness of the surface at the time when the indenter is pressed 1 μm from the outer surface of the surface layer is 1.0 N / mm 2 By setting the universal hardness at 7.0 N / mm or more, it is possible to suppress the occurrence of image density unevenness due to the deformation of the charging roller, which occurs when the charging roller is in contact with the electrophotographic photosensitive member in a stationary state for a long period of time. 2 By making the universal hardness equal to or less than 5.0 N / mm, deformation and cracking of the toner can be suppressed, and the absolute amount of irregular toner and finely powdered toner remaining on the photoconductor can be more reliably suppressed. 2 By doing so, the surface layer conforms to and deforms in response to the dirt, increasing the number of contact points between the convex portions made of conductive particles exposed on the surface of the surface layer and the dirt, thereby improving the efficiency of electron injection from the convex portions to the dirt.
[0117] The universal hardness of the surface of the surface layer of the charging roller is measured, for example, using a universal hardness tester (product name: Fischerscope HM2000XYp, manufactured by Fisher Instruments). The universal hardness is a physical property value that is determined by pressing an indenter into a measurement object while applying a load, and is expressed as "(test load) / (surface area of indenter under test load) (N / mm 2 A square pyramid or other indenter is pressed into the test object while applying a relatively small predetermined test load, and the surface area in contact with the indenter is calculated from the indentation depth at the point where a predetermined indentation depth is reached, and the universal hardness is calculated using the above formula.
[0118] <Surface layer protrusions derived from electronic conductive agent> In order to inject charges into the contaminants, it is preferable that there are convex portions on the surface of the surface layer originating from the exposed portions of the electronic conductive agent (conductive particles). The size of the convex portions originating from the exposed portions of the conductive particles is preferably 5.0 nm or more and 100.0 nm or less. By making the size 5.0 nm or more, the convex portions can function as starting points for more efficiently injecting charges into the contaminants. In addition, by making the size 100.0 nm or less, it is possible to suppress excessive injection of charges into the photoconductor. Note that the size of the convex portions means the average particle diameter 303 (number average particle diameter) of the conductive particles 301 in the portion exposed from the binder resin 302, as shown in FIG. 9. The method for measuring the size of the convex portions is to take an image of an arbitrary 2 μm square area using a SEM, measure the particle diameters of 20 particles randomly selected from the obtained image, and obtain the arithmetic average particle diameter. In addition, in order to inject electric charges into the dirt using the protrusions derived from the conductive fine particles, it is effective to control the number of protrusions. The number of protrusions derived from the exposed parts of the conductive fine particles is set to 2.0 μm in length and 2.0 μm in width (4.0 μm). 2It is preferable that the number of protrusions is 50 or more and 500 or less in the area (region). By making the number 50 or more, the number of protrusions as starting points for injecting electric charge into the dirt substance can be secured. Also, by making the number 500 or less, the injection of electric charge into the photoconductor can be suppressed. The number of protrusions can be calculated by taking an image of any 2 μm square region using a scanning electron microscope (SEM) and calculating the number of conductive points from the binarized image.
[0119] Next, a method of exposing the conductive fine particles on the surface of the surface layer will be described. When a surface layer is formed on the conductive layer of a conductive member by a dipping coating method, a skin layer is necessarily formed on the outermost surface of the surface layer. Therefore, in order to expose the conductive particles on the surface of the surface layer and generate a convex portion on the surface of the surface layer by the exposed portion, it is effective to remove the outermost skin layer. For example, by performing ultraviolet treatment, polishing method, electrolytic polishing method, chemical polishing method, ion milling method, etc., it is possible to remove the surface skin layer made of the binder resin and expose the conductive particles on the surface of the surface layer. In the present disclosure, since the hardness of the surface layer is low, the skin layer can be sufficiently removed by performing ultraviolet treatment, and the conductive fine particles can be exposed on the surface of the surface layer. Compared with polishing method, ultraviolet treatment is preferable because it can minimize damage to the surface layer and expose the conductive particles on the surface of the surface layer. The exposed state of the conductive particles can be confirmed using an atomic force microscope (AFM). A height image is acquired in tapping mode of the AFM. In this case, the part originating from the exposed part of the conductive particles is confirmed as a convex part. When a height image is acquired in a state where a skin layer after dip coating is present, the convex part is not confirmed. Furthermore, a phase image is acquired in tapping mode of the AFM. In this case, an image with a very large difference in shading contrast is obtained due to the small phase shift of the conductive particles and the hardness difference between the binder resin and the conductive particles. When a phase image is acquired in a state where a skin layer after dip coating is present, an image with a very small phase difference and low contrast difference is obtained.
[0120] <Roughening particles> The surface layer may contain roughening particles to the extent that the effect of this embodiment is not impaired. Examples of the roughening particles include the following: organic insulating particles such as acrylic resin, polycarbonate resin, styrene resin, urethane resin, fluororesin, and silicone resin; inorganic insulating particles such as titanium oxide, silica, alumina, magnesium oxide, strontium titanate, barium titanate, barium sulfate, calcium carbonate, mica, zeolite, and bentonite. By containing the roughening particles in the surface layer, the outer surface of the surface layer has convex portions derived from the roughening particles, and the surface shape of the surface layer can be greatly deformed. In the present disclosure, it is preferable to use flexible organic insulating particles as the roughening particles, since the deformation of the surface layer increases the contact opportunity with external additives, toner, and other contaminants. These particles may be used alone or in combination of two or more. The number average particle diameter of the roughening particles is not particularly limited, but is about 3 μm or more and 30 μm or less.
[0121] <Other additives> In this embodiment, other additives may be added to the surface layer as necessary to the extent that the effect of this embodiment is not impaired. Examples of additives that may be added include chain extenders, crosslinking agents, pigments, silicone additives, and catalysts such as amines and tin complexes. When a silicone additive is added to the surface layer, it is particularly preferable to add the silicone additive because it increases the resistance of the surface layer, imparts slipperiness to the surface layer, suppresses the injection of charges into the photoreceptor, and improves the wear resistance of the surface layer.
[0122] <Thickness of surface layer> The surface layer preferably has a thickness of 0.1 μm or more and 100 μm or less, and more preferably 1 μm or more and 50 μm or less. The thickness of the surface layer can be measured by cutting out a cross section of the conductive member with a sharp blade and observing it with an optical microscope or an electron microscope.
[0123] (2) Electrophotographic device The conductive member according to the present disclosure can be suitably used as a developing roller, a charging roller, a toner supply roller, a developing sleeve, a transfer roller, and a developing blade in an electrophotographic device as an electrophotographic image forming device. The conductive member can be applied to any of a non-contact type developing device and a contact type developing device using a magnetic one-component toner or a non-magnetic one-component toner, a developing device using a two-component toner, and a charging device. FIG. 8 is a schematic cross-sectional view showing an example of an electrophotographic device equipped with a conductive member according to the present disclosure as a developing roller of a contact-type developing device using one-component toner. The developing device 22 includes a toner container 20 containing toner 15 as one-component toner, a developing roller 16, a toner supply roller 19 that supplies toner to the developing roller 16, and a developing blade 21 that regulates the thickness of the toner layer on the developing roller 16. The developing roller 16 is located at an opening extending in the longitudinal direction in the toner container 20 and is placed in contact with the photoconductor 18. The photoconductor 18, the cleaning blade 26, the waste toner container 25, and the charging roller 24 may be disposed in the main body of the electrophotographic device. The developing device 22 is prepared for each color toner of black (Bk), cyan (C), magenta (M), and yellow (Y), enabling color printing.
[0124] The printing operation of the electrophotographic apparatus will now be described. The photoconductor 18 rotates in the direction of the arrow and is uniformly charged by a charging roller 24 for charging the photoconductor 18. Next, an electrostatic latent image is formed on the surface of the photoconductor 18 by a laser beam 23, which is an exposure means. The electrostatic latent image is visualized as a toner image (developed) by the development device 22, which applies toner 15 from a development roller 16 arranged in contact with the photoconductor 18. The development is a so-called reversal development in which a toner image is formed in the exposed portion. The toner image formed on the photoconductor 18 is transferred to an endless belt-like intermediate transfer body 32 by a transfer roller 29, which is a transfer member. Paper 34, which is a recording medium, is fed into the device by a paper feed roller 35 and a secondary transfer roller 36 and is transported together with the intermediate transfer body 32 carrying the toner image to a nip portion between the secondary transfer roller 36 and a driven roller 33, where the toner image is transferred to the paper 34. The intermediate transfer body 32 is operated by the driven roller 33, a drive roller 39, and a tension roller 38. Toner remaining on the intermediate transfer body 32 is cleaned by a cleaning device 37. A voltage is applied to the developing roller 16, developing blade 21, transfer roller 29 and secondary transfer roller 36 from a bias power supply 30. The paper 34 onto which the toner image has been transferred is fixed by a fixing device 27 and discharged outside the device, completing the printing operation. Meanwhile, residual toner remaining on the photoconductor 18 without being transferred is scraped off by a cleaning blade 26, which is a cleaning member for cleaning the photoconductor surface, and stored in a waste toner storage container 25. The cleaned photoconductor 18 repeats the above printing operation.
[0125] (3) Process cartridge The conductive member according to the present disclosure can be suitably used as a developing roller, a charging roller, a toner supply roller, a developing sleeve, a transfer roller, and a developing blade in a process cartridge. FIG. 9 is a schematic cross-sectional view of an example of a process cartridge according to one embodiment of the present disclosure. In FIG. 9, the conductive member is mounted as a developing roller 16. The process cartridge 17 is configured to be detachably attached to the main body of an electrophotographic device as shown in FIG. 8. The process cartridge 17 is an integrated device in which a developing device 22 including a developing roller 16 and a developing blade 21, a photoconductor 18, a cleaning blade 26, a waste toner storage container 25, and a charging roller 24 are integrated. The developing device 22 further includes a toner container 20, in which a toner 15 is filled. The toner 15 in the toner container 20 is supplied to the surface of the developing roller 16 by a toner supply roller 19, and a layer of the toner 15 having a predetermined thickness is formed on the surface of the developing roller 16 by the developing blade 21. EXAMPLES
[0126] Specific examples and comparative examples according to the present disclosure are given below. In the table below, "phr" is an abbreviation for "per hundred rubber" and represents the amount mixed per 100 parts by mass of rubber.
[0127] 1. Preparation of unvulcanized rubber composition for forming conductive layer used for forming conductive layer in Examples and Comparative Examples [1-1] Preparation of unvulcanized domain rubber composition (CMB) E-1 The unvulcanized domain rubber composition E-1 was prepared by mixing the materials in the amounts shown in Table 1 in a pressure kneader. A 6-liter pressure kneader (product name: TD6-15MDX, manufactured by Toshin Co., Ltd.) was used as the mixer. The mixing conditions were a filling rate of 70 vol%, a blade rotation speed of 30 rpm, and 16 minutes.
[0128] [Table 1]
[0129] [1-2] Preparation of unvulcanized matrix rubber composition E-1 The unvulcanized matrix rubber composition E-1 was prepared by mixing the materials in the amounts shown in Table 2 in a pressure kneader. A 6-liter pressure kneader (product name: TD6-15MDX, manufactured by Toshin Co., Ltd.) was used as the mixer. The mixing conditions were a filling rate of 70 vol%, a blade rotation speed of 30 rpm, and 16 minutes.
[0130] [Table 2]
[0131] [1-3] Preparation of unvulcanized rubber composition E-1 for forming conductive layer The unvulcanized domain rubber composition E-1 and the unvulcanized matrix rubber composition E-1 prepared in the above [1-1] and [1-2] were mixed in the ratio shown in Table 3 using a pressure kneader to obtain an unvulcanized rubber mixture. The mixer used was a 6-liter pressure kneader (product name: TD6-15MDX, manufactured by Toshin Co., Ltd.). The mixing conditions were a filling rate of 70 vol%, a blade rotation speed of 30 rpm, and 16 minutes.
[0132] [Table 3]
[0133] The unvulcanized rubber mixture obtained in [1-3] above and other materials were mixed using an open roll in the ratio shown in Table 4 to prepare an unvulcanized rubber composition E-1 for forming a conductive layer. The mixer used an open roll with a roll diameter of 12 inches (0.30 m). The mixing conditions were a front roll rotation speed of 10 rpm, a rear roll rotation speed of 8 rpm, a roll gap of 2 mm, and a total of 20 left and right turns, followed by 10 thin passes with a roll gap of 0.5 mm.
[0134] [Table 4]
[0135] [2-1] Preparation of unvulcanized rubber compositions E-2 to E-38 for domain formation [2-2] Preparation of unvulcanized rubber compositions E-2 to E-38 for forming the matrix Except for the types and amounts of rubber and conductive agent shown in Table 5, domain-forming unvulcanized rubber compositions E-2 to E-38 and matrix-forming unvulcanized rubber compositions E-2 to E-38 were prepared in the same manner as domain-forming unvulcanized rubber composition E-1 and matrix-forming unvulcanized rubber composition E-1.
[0136] [Table 5]
[0137] In Table 5, the unit of DBP absorption is (cm 3 / 100g). The Mooney viscosity values for raw rubber are the catalog values of each company, and the values for the unvulcanized rubber composition for domain formation and the unvulcanized rubber composition for matrix formation are Mooney viscosity ML (1+4) based on the Japanese Industrial Standards (JIS) K6300-1:2013, which were measured at the rubber temperature when all the materials constituting each rubber composition were being kneaded, and are expressed in Mooney units (M). The unit of SP value is (J / cm 3 ) 0.5 The same applies to the following tables.
[0138] [2-3] Preparation of unvulcanized rubber compositions E-2 to E-38 for forming conductive layer Unvulcanized rubber compositions E-2 to E-38 for forming a conductive layer were prepared in the same manner as the unvulcanized rubber composition E-1 for forming a conductive layer, except that the unvulcanized rubber composition for forming a domain, the unvulcanized rubber composition for forming a matrix, and other materials prepared in [2-1] and [2-2] above were mixed in the ratios shown in Table 6. The "blade rotation speed" in Table 6 is the blade rotation speed when the unvulcanized rubber composition for forming a domain and the unvulcanized rubber composition for forming a matrix were mixed in a pressure kneader prior to the preparation of the unvulcanized rubber composition for forming a conductive layer.
[0139] [Table 6]
[0140] Details of the materials listed by abbreviations in Tables 5 and 6 above are shown in Table 7. Table 7 also lists the materials used in the following examples and comparative examples.
[0141] [Table 7]
[0142] 3. Preparation of paint for forming surface layer [3-1] Preparation of surface layer forming paint S-1 The following materials were mixed and stirred: Polyether polyol (product name: PEG-1000, manufactured by Sanyo Chemical Industries, Ltd.): 52.0 parts by mass Isocyanate (product name: Millionate MR-400, manufactured by Tosoh Corporation): 48.0 parts by weight Carbon black (product name: MA-100, manufactured by Mitsubishi Chemical Corporation): 15.0 parts by mass -Urethane resin particles (product name: Art Pearl C-400T, manufactured by Negami Chemical Industries): 20.0 parts by weight Next, methyl ethyl ketone was added so that the total solid content ratio became 30 mass %, and then mixed with a sand mill. Next, the viscosity was further adjusted to 10 to 12 cps with methyl ethyl ketone to prepare a surface layer forming coating material S-1.
[0143] [3-2] Preparation of surface layer forming paints S-2 to S-10, 14 to 16 Except for the types and blending ratios of the binder resin and conductive agent as shown in Table 8, surface layer forming paints S-2 to S-16 were prepared in the same manner as surface layer forming paint S-1.
[0144] [3-3] Preparation of paint S-11 for forming surface layer The following materials were mixed and stirred: Acrylic polyol (product name: Acrydic A817, manufactured by DIC Corporation): 75.0 parts by mass Melamine resin (product name: U-Ban 20SB, manufactured by Mitsui Chemicals): 25.0 parts by weight Carbon black (product name: Printex 25, manufactured by Orion Engineered Carbons): 10.0 parts by weight Lithium salt compound (product name: F-TOP EF-N115, manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd.): 2.0 parts by mass -Urethane resin particles (product name: Art Pearl C-400T, manufactured by Negami Chemical Industries): 20.0 parts by weight Next, methyl ethyl ketone was added so that the total solid content ratio was 30% by mass, and then mixed with a sand mill. Next, the viscosity was further adjusted to 10 to 12 cps with methyl ethyl ketone to prepare a surface layer forming coating material S-11.
[0145] [3-4] Preparation of paint S-12 for forming surface layer 100.0 parts by mass of polyamide resin (product name: Toresin EF-30T, manufactured by Teikoku Chemical Industries Co., Ltd.) was added to 2000 g of methanol and dissolved by stirring. Next, 20.0 parts by mass of urethane resin particles (product name: Art Pearl C-400T, manufactured by Negami Chemical Industries, Ltd.) were added and mixed with a sand mill. Next, the viscosity was further adjusted to 10 to 12 cps with methanol to prepare a surface layer forming paint S-12.
[0146] [3-5] Preparation of paint S-13 for forming surface layer 100.0 parts by mass of acrylic resin (product name: Almatex L1060, manufactured by Mitsui Chemicals) was added to 300 g of toluene and stirred to dissolve. Next, 11.0 parts by mass of urethane resin fine particles (product name: Art Pearl C-400T, manufactured by Negami Chemical Industries) were added and mixed with a sand mill. Next, the viscosity was adjusted to 10 to 12 cps with toluene to prepare a surface layer forming paint S-13.
[0147] [Table 8]
[0148] *Table 9 shows the material types related to the product names listed in Table 8.
[0149] [Table 9]
[0150] [Example 1] Manufacturing method of electrophotographic rollers E-1 to E-38 (1) Formation of a conductive layer A core bar with a total length of 252 mm and an outer diameter of 6 mm, made of free-cutting steel with a surface treated with electroless nickel plating, was prepared as the support body, which is a conductive mandrel. Next, a die with an inner diameter of 16.0 mm was attached to the tip of a crosshead extruder having a mechanism for feeding a conductive support and a mechanism for discharging an unvulcanized rubber roller, and the temperature of the extruder and the crosshead was adjusted to 80° C., and the conveying speed of the conductive support was adjusted to 60 mm / sec. Under these conditions, the unvulcanized rubber composition E-1 for forming a conductive layer was fed from the extruder, and the outer periphery of the conductive support was covered with the unvulcanized rubber composition in the crosshead, to obtain an unvulcanized rubber roller. Next, the unvulcanized rubber roller was placed in a hot air vulcanizing furnace at 170°C and heated for 60 minutes to vulcanize the unvulcanized rubber composition, obtaining a roller with a conductive layer formed on the outer periphery of the conductive support. After that, both ends of the conductive layer were cut off, and the surface of the conductive layer was polished with a rotary grindstone. As a result, a roller was obtained with a conductive layer having a crown shape with a diameter of 12.0 mm at each position 90 mm from the center to both ends and a diameter of 12.2 mm at the center.
[0151] (2) Formation of the surface layer The roller with the conductive layer obtained in (1) was turned vertically with its lengthwise direction, and the upper end was held and immersed in the paint S-1 for forming a surface layer to form a coating film of the paint on the surface of the conductive layer. The immersion time was 9 seconds, and the roller pull-up speed was adjusted so that the initial speed was 20 mm / sec and the final speed was 2 mm / sec, and the speed was changed linearly with time between 20 mm / sec and 2 mm / sec. After coating, the roller was air-dried for 30 minutes at 23°C. Further, by performing a heat treatment at a temperature of 150° C. for 1 hour, an electrophotographic roller according to Example 1 having a surface layer with a thickness of 15 μm on the outer periphery of the conductive layer was produced.
[0152] 5. Characterization [5-1] Confirmation of the presence or absence of matrix-domain (MD) structure The presence or absence of the matrix-domain structure according to the present disclosure in the conductive layer was confirmed by the following method. First, a slice was cut out using a razor so that a cross section perpendicular to the circumferential direction of the conductive layer could be observed. Next, platinum was vapor-deposited on the surface of the slice corresponding to the cross section of the conductive layer. Then, the platinum-deposited surface of the slice was observed at a magnification of 1,000 times using a scanning electron microscope (SEM) (product name: S-4800, manufactured by Hitachi High-Technologies Corporation) to obtain an SEM image. The presence or absence of the matrix-domain structure was confirmed from the obtained SEM image. This observation was performed on sections taken from a total of 20 points, with the developing roller (longitudinal length: 230 mm) divided into 5 equal parts in the longitudinal direction and 4 equal parts in the circumferential direction and one point selected from each area. The results are shown in the "MD structure" column in Tables 11-1, 20-1, and 26-1 as "Y" if the matrix domain structure was confirmed, and "N" if it was not confirmed. As a result of this evaluation, the matrix-domain structure of the conductive layer according to Example 1 was such that a plurality of domains 6b were dispersed in a matrix 6a in an SEM image, and the conductive paths were interrupted, as shown in Fig. 5. Meanwhile, the matrix was connected.
[0153] [5-2] Frequency 1×10 6 Hz~1×10 7 Impedance slope in Hz and frequency 1×10 -2 Hz~1×10 1 Calculating impedance in Hz The impedance was measured as follows. First, as a pretreatment, platinum was vapor-deposited onto the outer surface of the developing roller while rotating it to create a measurement electrode. At this time, a masking tape was used to create an electrode with a width of 1.5 cm and uniformity in the circumferential direction. By forming this electrode, the contribution of the contact area between the measurement electrode and the conductive member due to the surface roughness of the conductive member can be reduced as much as possible. Next, an aluminum sheet was wrapped around the electrodes with no gaps, and the aluminum sheet was connected to the measurement electrodes of an impedance measuring device (product names: Solartron 1260 and Solartron 1296; manufactured by Solartron Corporation).
[0154] A schematic diagram of the state in which the measurement electrodes are formed on the developing roller is shown in Figure 10. In Figure 10, 101 is a conductive support, 102 is a conductive layer having a matrix domain structure, 103 is a platinum vapor deposition layer, and 104 is an aluminum sheet. Figure 11 shows a cross-sectional view of a conductive member with a measurement electrode formed thereon. 111 is a conductive support, 112 is a conductive layer with a matrix domain structure, 113 is a surface layer, 114 is a platinum vapor deposition layer, and 115 is an aluminum sheet. As shown in Figure 11, it is important to sandwich the conductive layer with a matrix domain structure and the surface layer between the conductive support and the measurement electrode. The aluminum sheet was then connected to a measurement electrode on the side of an impedance measuring device (Solatron 1260 and Solartron 1296, manufactured by Solartron Corporation). Impedance measurement was performed by using the conductive support and the aluminum sheet as two electrodes for measurement.
[0155] The impedance was measured at a temperature of 23°C and a relative humidity of 50%, with an oscillation voltage of 1Vpp, a DC current of 10V, and a frequency of 1×10 -2 Hz~10 7 The absolute impedance value was obtained by measuring the impedance at five points when the frequency changed by one digit. The measurement results were then used to create a graph in which the absolute impedance value and frequency were plotted on a logarithmic scale. From the graph, it was found that the impedance was 1.0×10 -2 ~1.0×10 1 The impedance at Next, the surface layer was peeled off from the developing roller A1, and platinum was directly vapor-deposited on the surface of the conductive layer to prepare a measurement electrode. Then, the impedance was measured in the same manner as above, and a graph was created. From this graph, it was found that the impedance of 1×10 6 Hz~1×10 7 The slope in Hz was calculated. -2 ~1.0×10 1 The impedance was calculated in Hz. The developing roller A1 (length in the longitudinal direction: 230 mm) was divided into 5 equal regions in the longitudinal direction, and measurement electrodes were formed at 1 point in each region (total of 5 points), and the above measurement was performed. The average value was taken as the impedance slope. Furthermore, the impedance of the conductive support was measured in the same manner as above, except that a platinum electrode was provided on the outer surface of the conductive support.
[0156] [5-3] Measurement of matrix volume resistivity The volume resistivity of the matrix was measured in contact mode using a scanning probe microscope (SPM) (product name: Q-Scope250, manufactured by Quesant Instrument Corporation) as follows. The measurement environment was a temperature of 23° C. and a relative humidity of 50%. First, a section having a thickness of about 2 μm was cut out from the conductive layer of the developing roller at a cutting temperature of −100° C. using a microtome (trade name: Leica EM FCS, manufactured by Leica Microsystems). Next, the section was placed on a metal plate so that one surface of the section corresponding to the cross section of the conductive layer was in contact with the surface of the metal plate. Then, the cantilever of the SPM was brought into contact with the portion of the surface of the section opposite to the surface in contact with the surface of the metal plate that corresponds to the matrix. Next, a voltage of 50 V was applied to the cantilever, and the current value was measured. The surface shape of the slice was observed with an SPM, and the thickness of the measurement point was calculated from the height profile obtained. Furthermore, the area of the recess at the contact point of the cantilever was calculated from the observation result of the surface shape. The volume resistivity was calculated from the thickness and the area of the recess, and was set as the volume resistivity of the matrix. The slices were obtained by dividing the developing roller (longitudinal length: 230 mm) according to Example 1 into 5 equal parts in the longitudinal direction and 4 equal parts in the circumferential direction, and one point was taken from each area at random, for a total of 20 points, and the above measurement was performed on each slice. The average value of the measured values at each measurement point was calculated. The obtained results are shown in Tables 11-1, 20-1, and 26-1 as the "volume resistivity" of the "matrix".
[0157] [5-4] Measurement of volume resistivity of domain The volume resistivity of the domain was measured in the same manner as in the measurement of the volume resistivity of the matrix, except that the contact position of the cantilever was set to the point corresponding to the domain, and the voltage applied to the cantilever was set to 1 V. The average value of the values at each measurement point was calculated. The results are shown in Tables 11-1, 20-1, and 26-1 as the "volume resistivity" of the "domain."
[0158] [5-5] Ratio of the volume resistivity of the matrix to the volume resistivity of the domain The ratio of the volume resistivities of the matrix and the domain (log(R1 / R2)) was calculated by plotting the common logarithm of the volume resistivity R1 of the matrix and the common logarithm of the volume resistivity R2 of the domain. The results are shown in Tables 11-1, 20-1, and 26-1 as the "resistance ratio" of the "matrix domain."
[0159] [5-6] Measuring the shape of the domain To assess the size of the domain, the following measurements were made: That is, platinum was vapor-deposited on the surface of the slice prepared in the measurement of the volume resistivity of the matrix, which corresponds to the cross section of the conductive layer. Next, the platinum-deposited surface was photographed at 1,000 times magnification using an SEM (product name: S-4800, manufactured by Hitachi High-Technologies Corporation) to obtain an SEM image. Next, the SEM image was converted to 8-bit grayscale using image processing software "Image-pro plus" (product name, manufactured by Media Cybernetics Co., Ltd.) to obtain a monochrome image with 256 gradations. Next, the black and white of the image was inverted so that the domains in the monochrome image became white, and a binarization threshold was set for the brightness distribution of the image based on the algorithm of Otsu's discriminant analysis method to obtain a binary image. Next, for the binary image, when the thickness of the conductive layer is T, observation areas of 15 μm square were placed at any three locations, a total of nine locations, within the area corresponding to the thickness area from the outer surface of each of the three slices to a depth of 0.1T to 0.9T. Then, using the counting function of the image processing software, the following items were calculated for the domains in each observation region.
[0160] ·Perimeter: A Envelope perimeter: B Ratio of A and B: A / B The percentage of domains that meet requirement (B3) out of all observed domains (number%)
[0161] The developing member was divided into 5 equal parts in the longitudinal direction and 4 equal parts in the circumferential direction, and the above measurements were carried out on slices taken from these 20 regions, and the arithmetic mean value of the calculation results for each of the above items was used to evaluate the domain.
[0162] It should be noted that "A" in requirement (B3) is the perimeter 72 of domain 71 observed in the observation area, as shown in Fig. 6. Also, "B" is the length (envelope perimeter) of convex envelope 73 of the domain, indicated by a dashed line. The results are shown in Tables 11-2, 20-2, and 26-2 as "perimeter A," "envelope perimeter B," "A / B (average value)," and "number of domains satisfying requirement (B3)," respectively.
[0163] [5-7] Measurement of interdomain distance Except for using the domain distance counting function of the image processing software, the developing roller was divided into 5 equal parts in the longitudinal direction and 4 equal parts in the circumferential direction, and the arithmetic average of the above measurement results for the 20 regions was taken as the domain distance (Dm). The results obtained are shown as "Distance" in the "Matrix" in Tables 11-1, 20-1, and 26-1, and as "Domain distance Dm" in Tables 11-2, 20-2, and 26-2.
[0164] [5-8] Volume fraction measurement The volume fraction of the domain was determined from a three-dimensional image of the sample reconstructed from multiple cross-sectional images of the sample taken from the conductive layer using a FIB-SEM. Note that the FIB-SEM is a composite device consisting of a FIB (Focused Ion Beam) device and a SEM (scanning electron microscope). Specifically, cubic samples with a side length of 9 μm were taken from nine locations on the conductive layer. In the case of a roller shape, the locations were (1 / 4)L, (2 / 4)L, and (3 / 4)L from one end, where L is the length of the conductive layer in the longitudinal direction, and one sample was taken from each position at 120 degrees around the roller. At this time, the center of gravity of each sample was set to coincide with the midpoint in the thickness direction of the conductive layer. Next, for each sample, exposure of the cross section using FIB and taking SEM images of the exposed cross section were repeated to obtain a group of slice images. The slice interval of the sample was 60 nm. The obtained slice image group was used to reconstruct a three-dimensional image using 3D visualization and analysis software Avizo (manufactured by F.E.I. Co., Ltd.). From the obtained three-dimensional image, the volume of the domain in the 27 unit cubes with a side length of 3 μm contained in one cubic sample with a side length of 9 μm was calculated. The results are shown as "domain volume fraction" in Tables 11-1, 20-1, and 26-1.
[0165] [5-9] Uniform distribution of domains The uniform dispersion of the domains in the conductive layer was determined by measuring the conductive layer in three dimensions using a FIB-SEM, as well as measuring the volume fraction of the domains. The fact that the conductive domains are arranged three-dimensionally evenly and densely in the conductive layer was verified by the above-mentioned method. Here, as described above, 3D measurements were performed using FIB-SEM, and it was evaluated whether at least 8 samples out of the cubic samples (sample cubes) with one side measuring 9 μm satisfied the following requirement (B1).
[0166] Requirement (B1): "When one cubic sample is divided into 27 unit cubes each having a side length of 3 μm, and the volume Vd of the domain contained in each unit cube is calculated, Vd is 2.7 to 10.8 μm. 3 There must be at least 20 unit cubes in which As described above, the effect of the present disclosure is enhanced by increasing the number of unit cubes each having a side length of 3 μm among sample cubes each having a side length of 9 μm that satisfy requirement (B1). The results obtained are shown in Tables 11-2, 20-2, and 26-2 as "number of cubes that satisfy requirement (B1)."
[0167] [5-10] The ratio of the cross-sectional area of the electronic conductive material contained in the domain to the cross-sectional area of the domain The platinum-deposited surface of the platinum-deposited slice prepared in the above [5-6. Measurement of the domain shape] was photographed at a magnification of 20,000 times using a scanning electron microscope (SEM) (product name: S-4800, manufactured by Hitachi High-Technologies Corporation) at a location corresponding to the 15 μm square observation area placed on the binary image in the evaluation in 5-6. above, to obtain an SEM image. The obtained SEM image was converted to 8-bit grayscale using an image analyzer (product name: LUZEX-AP, manufactured by Nireco Corporation) to obtain a monochrome image with 256 gradations. Next, the black and white of the image were inverted so that the domains in the monochrome image became white, and a binarization threshold was set for the brightness distribution of the image based on the algorithm of Otsu's discriminant analysis method, to obtain a binary image. Next, an observation area large enough to accommodate one domain was extracted from the obtained binary image. Then, the cross-sectional area Sd of one domain and the cross-sectional area Sc of the electronic conductive agent (carbon black) in the domain were calculated. From the cross-sectional area Sc of the obtained electronic conductive agent (carbon black) and the cross-sectional area Sd of the domain, μ=Sc / Sd was calculated to obtain the ratio of the cross-sectional area of the electronic conductive agent contained in the domain to the cross-sectional area of the domain. This was performed for each domain in the observation region. From the obtained results, the average value of the cross-sectional area ratio of the electronic conductive agent "μ", the standard deviation of the cross-sectional area ratio of the electronic conductive agent "σ", the cross-sectional area ratio (average) of requirement (B2) "μ / σ", and the "% number of domains satisfying requirement (B2)" were calculated. These are shown in Tables 11-2, 20-2, and 26-2.
[0168] [5-11] Volume resistivity of surface layer The volume resistivity of the surface layer was measured in the conductive mode using an atomic force microscope (AFM) (Q-scope250: Quesant). First, the surface layer of the developing roller was cut into a sheet with a width of 2 mm and a length of 2 mm using a manipulator, and platinum was evaporated onto one side of the surface layer. Next, a DC power source (6614C: Agilent) was connected to the platinum-evaporated surface and 10 V was applied, and the free end of the cantilever was brought into contact with the other side of the surface layer, and a current image was obtained through the AFM body. This measurement was performed on 100 randomly selected points on the surface of the entire surface layer, and the "volume resistivity" was calculated from the average current value of the top 10 lowest current values and the average film thickness of the surface layer. The evaluation results are shown in Table 8. The measurement conditions are as follows. Measurement mode: contact Cantilever: CSC17 Measurement range: 10nm x 10nm Scan rate: 4Hz Applied voltage: 10V
[0169] [Examples 2 to 5] The electrophotographic rollers of Examples 2 to 5 were obtained in the same manner as in Example 1, except that the unvulcanized rubber composition for forming the conductive layer and the coating material for forming the surface layer were changed to those shown in Table 10.
[0170] [Example 6] A conductive layer was prepared in the same manner as in Example 1, except that the unvulcanized rubber composition E-6 for forming a conductive layer was used. Then, the surface of the conductive layer was dip-coated with the coating material S-11 for forming a surface layer, and heated at a temperature of 140° C. for 30 minutes to prepare an electrophotographic roller of Example 6 having a surface layer with a thickness of 15 μm on the outer periphery of the conductive layer.
[0171] [Example 7] Except for using the unvulcanized rubber composition E-7 for forming a conductive layer, the conductive layer was prepared in the same manner as in Example 1. The paint S-12 for forming a surface layer was applied to the surface of the conductive layer by dip coating, and the surface was heated at a temperature of 120° C. for 30 minutes to prepare an electrophotographic roller of Example 7 having a surface layer with a thickness of 15 μm on the outer periphery of the conductive layer.
[0172] [Example 8] An electrically conductive layer was prepared in the same manner as in Example 1, except that the unvulcanized rubber composition for forming an electrically conductive layer E-8 was used. The surface of the conductive layer was dip-coated with the surface layer forming paint S-13 and then heat-treated at a temperature of 140°C for 1 hour to produce an electrophotographic roller of Example 8 having a surface layer with a thickness of 15 μm on the outer periphery of the conductive layer.
[0173] [Examples 9 to 34] The electrophotographic rollers according to Examples 9 to 34 were obtained in the same manner as in Example 1, except that the unvulcanized rubber compositions for forming the conductive layer and the coating materials for forming the surface layer were used in the combinations shown in Table 10.
[0174] [Example 35] A core bar with an outer diameter of 6 mm was prepared by electroless nickel plating on the surface of free-cutting steel. Next, an adhesive "Metalock U-20" (product name, manufactured by Toyo Kagaku Kenkyusho) was applied to the entire circumference of the core bar, except for 15 mm at each end, using a roll coater, to produce the support according to this example. An electrophotographic roller of Example 35 was obtained in the same manner as in Example 1, except that this support was used and that the unvulcanized rubber composition for forming a conductive layer and the coating material for forming a surface layer shown in Table 10 were used. The impedance of the conductive support in this example was measured by providing a platinum electrode on the surface of the adhesive layer (resin layer) on the core metal.
[0175] [Example 36] A round bar with an outer diameter of 8 mm was formed by injection molding using a conductive thermoplastic resin (product name: Torayca TLP1060; manufactured by Toray Industries, Inc.). The round bar was then polished to prepare a support made of conductive resin with an outer diameter of 6 mm and the same shape as the free-cutting steel support used in Example 1. An electrophotographic roller of Example 36 was obtained in the same manner as in Example 1, except that this support was used and that the unvulcanized rubber composition for forming a conductive layer and the coating material for forming a surface layer shown in Table 10 were used.
[0176] [Example 37] The conductive resin core used in Example 36 was prepared. Next, using a roll coater, Metalock U-20 (trade name, manufactured by Toyo Kagaku Kenkyusho) was applied as an adhesive to the entire circumference of the core except for 15 mm at each end. The roller for electrophotography of Example 37 was obtained in the same manner as in Example 1, except that the support was used and the unvulcanized rubber composition for forming the conductive layer and the coating material for forming the surface layer shown in Table 10 were used. The impedance of the conductive support in this example was measured by providing a platinum electrode on the surface of the adhesive layer (resin layer) on the core.
[0177] [Example 38] A round bar having an outer diameter of 8 mm was formed by injection molding using PPS resin (product name: Torelina A503-X05; manufactured by Toray Industries, Inc.). The round bar was then polished to prepare a PPS resin core (insulating resin core) having an outer diameter of 6 mm, which had the same shape as the free-cutting steel core used in Example 1. Platinum deposition was applied to the entire outer surface of the obtained PPS resin core to form a mandrel. Next, an adhesive was applied to the mandrel in the same manner as in Example 37. The electrophotographic roller of Example 38 was produced in the same manner as in Example 1, except that the unvulcanized rubber composition for forming a conductive layer and the coating material for forming a surface layer shown in Table 10 were used as the support.
[0178] [Table 10]
[0179] The results of the evaluations [5-1] to [5-10] of the conductive rollers according to Examples 1 to 38 are shown in Tables 11-1 to 11-2. The result of the evaluation [5-11] is shown in Table 8.
[0180] [Table 11-1]
[0181] [Table 11-2]
[0182] 6. Evaluation as a developing roller The obtained electrophotographic rollers according to Examples 1 to 38 were evaluated as developing rollers in the following manner.
[0183] [6-1] Image (fog) evaluation The electrophotographic rollers according to the respective Examples and Comparative Examples were loaded as developing rollers into a magenta toner cartridge for a laser printer (product name: HP Color Laserjet Enterprise CP4515dn, manufactured by HP) having the configuration shown in Fig. 9, and fog images were evaluated. In order to evaluate in a high-speed process, the laser printer was modified so that the number of sheets output per unit time was 50 sheets / minute for A4 size paper, which was greater than the number of sheets output in the original. The magenta toner cartridge with each developing roller loaded was loaded into the laser printer, and placed in a high-temperature and high-humidity environment with a temperature of 32°C and a relative humidity of 85%RH, and then left for 6 hours. Next, an image in which the letter "E" of the alphabet with a size of 4 points was printed so that the coverage rate of the area of A4 size paper was 1% (hereinafter also referred to as "E letter image") was continuously output on a predetermined number of copy papers. Then, a solid white image was output on a new copy paper, and the printer was stopped during the output of the solid white image. At this time, the toner attached on the photoconductor was peeled off with a tape (product name: CT18, manufactured by Nichiban Co., Ltd.), and the reflectance was measured with a reflection densitometer (product name: TC-6DS / A, manufactured by Tokyo Denshoku Co., Ltd.). The amount of decrease in reflectance (%) based on the reflectance of the tape was measured and this was taken as the fogging value. Based on these fogging values, evaluation was performed according to the following criteria. Rank A: The fogging value is less than 1.5%. Rank B: The fog value is 1.5% or more and less than 3.0%. Rank C: The fog value is 3.0% or more and less than 5.0%. Rank D: The fogging value is 5.0% or more.
[0184] [6-2] Toner charge amount In order to evaluate the charge imparting ability of the electrophotographic roller to the toner, the charge amount was measured. During the evaluation of the fog image, the toner carried on the narrower portion of the electrophotographic roller between the toner regulating blade and the photoreceptor abutment position was collected by suction using a metal cylindrical tube and a cylindrical filter. At that time, the charge amount stored in the capacitor through the metal cylindrical tube and the mass of the toner sucked in were measured. The charge amount was measured using a measuring device (product name: 8252) manufactured by ADC Corporation. From these values, the charge amount (μC / g) per unit mass was calculated. When a negatively charged toner is used, the sign of the charge amount per unit mass is negative, and the larger the absolute value, the higher the charge imparting ability of the developing roller. The value obtained by the measurement was taken as the toner charge amount.
[0185] [6-3] Toner charge distribution In order to evaluate the spread of the charge amount of the toner, the charge amount distribution was measured. The charge distribution was measured using a powder measurement charge / particle size distribution measuring instrument (product name: E-spart Analyzer Model EST-III, manufactured by Hosokawa Micron Corporation). Except for this, the charge distribution was measured in the same manner as in the measurement of the toner charge. The number of particles measured was approximately 3000. The standard deviation was calculated from the obtained charge distribution, and the obtained value was regarded as the initial charge distribution of the toner.
[0186] [6-4] High temperature and high humidity / low temperature and low humidity cycle test A test for alternately evaluating in a high temperature / high humidity environment and a low temperature / low humidity environment (hereinafter referred to as an environmental cycle test) was conducted as follows: First, in the same manner as in the image (fog) evaluation, a magenta toner cartridge equipped with each electrophotographic roller was loaded into the laser printer, and the printer was placed in a high temperature / high humidity environment (hereinafter referred to as H / H) with an air temperature of 32°C and a relative humidity of 85%, and then left for 30 minutes. Next, in this environment, an image (hereinafter also referred to as "E letter image") in which the letter "E" in 4 points is printed so that the coverage rate of the area of A4 size paper is 1% was continuously output on 500 sheets of copy paper. Next, the toner cartridge and the laser printer were placed in a low temperature and low humidity environment (hereinafter referred to as L / L) with an air temperature of 15°C and a relative humidity of 10%, and left for 30 minutes. Next, in this environment, an image (hereinafter also referred to as "E letter image") in which the letter "E" in 4 points is printed so that the coverage rate of the area of A4 size paper is 1% was continuously output on 500 sheets of copy paper. This H / H and L / L image output constituted one cycle, and a total of five cycles were repeated.
[0187] Next, the toner charge amount and the toner charge amount distribution were measured in the same manner as the measurement before the environmental cycle test. Furthermore, the electrophotographic roller was taken out of the toner cartridge, and the state of destruction in the vicinity of the surface layer of the electrophotographic roller was evaluated according to the following criteria.
[0188] Rank A: No damage was observed over the entire electrophotographic roller. Rank B: Minor damage was observed only on the end of the electrophotographic roller (within a range of 1.5 cm from the end of the elastic layer in the longitudinal direction). Rank C: Minor damage was observed in areas other than the ends of the electrophotographic roller. Rank D: Damage was found anywhere in the entire electrophotographic roller, causing problems in the images.
[0189] The results of evaluations [6-1] to [6-4] are shown in Table 11-3.
[0190] [Table 11-3]
[0191] [Comparative Example 1] The materials in the amounts shown in Table 12 were mixed in a pressure kneader. A 6-liter pressure kneader (product name: TD6-15MDX, manufactured by Toshin Co., Ltd.) was used as the mixer. The mixing conditions were a filling rate of 70 vol%, a blade rotation speed of 30 rpm, and 16 minutes. A conductive layer was formed on a support in the same manner as in Example 1, except that the obtained unvulcanized rubber composition was used as it is as an unvulcanized rubber composition for forming a conductive layer. Next, the conductive layer was dip-coated with the surface layer coating material S-1, and heat-treated at a temperature of 150° C. for 1 hour to form a surface layer with a thickness of 15 μm on the outer periphery of the conductive layer, thereby producing an electrophotographic roller of Comparative Example 1.
[0192] [Table 12]
[0193] [Comparative Example 2] An electrophotographic roller of Comparative Example 2 was produced in the same manner as in Comparative Example 1, except that the amounts of each material shown in Table 13 were used.
[0194] [Table 13]
[0195] [Comparative Example 3] The materials shown in Table 14 were mixed in a pressure kneader to obtain an unvulcanized rubber composition for forming a domain. A 6-liter pressure kneader (product name: TD6-15MDX, manufactured by Toshin Co., Ltd.) was used as the mixer. The mixing conditions were a filling rate of 70 vol%, a blade rotation speed of 30 rpm, and 16 minutes.
[0196] [Table 14]
[0197] Next, the materials shown in Table 15 were mixed in a pressure kneader to obtain an unvulcanized rubber composition for forming a matrix. A 6-liter pressure kneader (product name: TD6-15MDX, manufactured by Toshin Co., Ltd.) was used as the mixer. The mixing conditions were a filling rate of 70 vol%, a blade rotation speed of 30 rpm, and 16 minutes.
[0198] [Table 15]
[0199] Next, the unvulcanized rubber composition for forming a domain and the unvulcanized rubber composition for forming a matrix prepared above were mixed in the amounts shown in Table 16 to obtain an unvulcanized rubber mixture. A 6-liter pressure kneader (product name: TD6-15MDX, manufactured by Toshin Co., Ltd.) was used as the mixer. The mixing conditions were a filling rate of 70 vol%, a blade rotation speed of 30 rpm, and 16 minutes.
[0200] [Table 16]
[0201] 100 parts by mass of the unvulcanized rubber mixture obtained above, 3 parts by mass of sulfur (trade name: Sulfac PMC, manufactured by Tsurumi Chemical Industry Co., Ltd.), and 2 parts by mass of tetrabenzyl thiuram disulfide (trade name: TBZTD, manufactured by Sanshin Chemical Industry Co., Ltd.) were mixed to prepare an unvulcanized rubber composition EC-3 for molding conductive members. An open roll with a roll diameter of 12 inches (0.30 m) was used for the mixer. The mixing conditions were a front roll rotation speed of 10 rpm, a rear roll rotation speed of 8 rpm, a roll gap of 2 mm, and a total of 20 left and right turns, and then a roll gap of 0.5 mm and 10 thin passes. An electrophotographic roller of Comparative Example 3 was obtained in the same manner as in Example 1, except that the unvulcanized rubber composition EC-3 for forming a conductive layer obtained in this manner was used.
[0202] [Comparative Example 4 to Comparative Example 14] <Preparation of Unvulcanized Rubber Compositions EC-4 to EC-8, EC-11, and EC-12 for Domain Formation> Unvulcanized rubber compositions for domain formation EC-4 to EC-8, EC-11, and EC-12 were prepared in the same manner as in Comparative Example 3, except that the materials shown in Table 17-1 were used as the rubber and conductive agent in the blending ratios shown in Table 17-1.
[0203] [Table 17-1]
[0204] <Preparation of Unvulcanized Rubber Compositions EC-4 to EC-12 for Matrix Formation> Unvulcanized rubber compositions for matrix formation EC-4 to EC-12 were prepared in the same manner as in Comparative Example 3, except that the materials shown in Table 17-2 were used as rubber types and additives in the compounding ratios shown in Table 17-2. Table 17-2 also shows the compositions of the rubber compositions for matrix formation prepared in Comparative Examples 1 to 3.
[0205] [Table 17-2]
[0206] <Preparation of Unvulcanized Rubber Compositions EC-4 to EC-12 for Forming Conductive Layer> Unvulcanized rubber compositions for forming a conductive layer EC-4 to EC-12 were prepared in the same manner as in Comparative Example 3, except that the unvulcanized rubber composition for forming a domain, the unvulcanized rubber composition for forming a matrix, and other materials were used in the blending ratios shown in Table 18.
[0207] [Table 18]
[0208] <Preparation of Electrophotographic Rollers According to Comparative Examples 4 to 10 and 12 to 14> A conductive layer was formed on a support in the same manner as in Comparative Example 3, except that unvulcanized rubber compositions EC-4 to EC-10 and 12 for forming a conductive layer were used. Next, electrophotographic rollers according to Comparative Examples 4 to 10 and 12 to 14 were produced in the same manner as in Comparative Example 3, except that the coating material shown in Table 19 was used as the surface layer forming coating material.
[0209] <Preparation of Electrophotographic Roller According to Comparative Example 11> The unvulcanized rubber composition EC-11 for forming a domain was heated and vulcanized alone, and then frozen and crushed to prepare rubber particles. Except for using this rubber particle as a material for forming a domain, various materials were mixed in the blending ratio shown in Table 18 to prepare an unvulcanized rubber composition EC-11 for forming a conductive layer. Except for using this unvulcanized rubber composition EC-11 for forming a conductive layer, a conductive layer was formed on a support in the same manner as in Comparative Example 3. Next, an electrophotographic roller of Comparative Example 11 was prepared in the same manner as in Comparative Example 3, except for using the coating material shown in Table 19 for forming a surface layer. In the electrophotographic roller of Comparative Example 11, the conductive layer contains large, anisotropic conductive rubber particles formed by freeze-pulverizing crosslinked rubber, so that the conductive paths in the conductive layer are formed non-uniformly, which is equivalent to a state in which the thickness of the domain is large. As a result, the slope of the impedance at high frequencies is -1.
[0210] <Preparation of Electrophotographic Rollers According to Comparative Examples 13 and 14> Electrophotographic rollers according to Comparative Examples 13 and 14 were produced in the same manner as in Comparative Example 5, except that the surface layer forming paint S-15 or S-16 was used.
[0211] The obtained conductive rollers according to Comparative Examples 1 to 14 were subjected to evaluations [5-1] to [5-10] and evaluations [6-1] to [6-4]. The results of evaluations [5-1] to [5-10] are shown in Tables 20-1 to 20-2, and the results of evaluations [6-1] to [6-4] are shown in Table 21.
[0212] [Table 19]
[0213] [Table 20-1]
[0214] [Table 20-2]
[0215] [Table 21]
[0216] The developing rollers according to Examples 1 to 38 have the configuration of the present disclosure in the conductive layer. The impedance in the low frequency range measured between the outer surface of the developing roller and the outer surface of the support is 1.0×10 4 ~1.0×10 11 Because it is Ω, the charge distribution is sharp and the fog value is very small, resulting in a high-quality image. Furthermore, in Examples 1 to 5 and Examples 10 to 38 in which the surface layer is made of urethane resin, no damage occurs near the surface even after the environmental cycle test, and a sharp charge distribution and good image characteristics are maintained. On the other hand, in the developing rollers of Comparative Examples 1 to 12, which do not have the conductive layer according to the present disclosure, and Comparative Examples 13 and 14, in which the impedance in the low frequency range measured between the outer surface of the developing roller and the outer surface of the support is outside the range of the present disclosure, the charge distribution was large and the image quality was not good.
[0217] [Example 39] [Making the development blade] The conductive layer-forming unvulcanized rubber composition E-2 was pressed into a mold having a width of 250 mm, a length of 150 mm, and a thickness of 0.7 mm by a pressure press machine, and treated at a temperature of 160° C. for 10 minutes to obtain a rubber sheet 1 having a thickness of 0.7 mm. The obtained rubber sheet 1 was cut into a width of 215 mm and a length of 12 mm. In addition, a sheet metal having the same shape as the sheet metal used in the developing blade of the electrophotographic process cartridge described later was prepared. The above-mentioned rubber sheet was bonded to this sheet metal using an adhesive. At this time, the length of the part overlapping with the sheet metal of the 12 mm length of the rubber sheet was set to 4.5 mm, and the remaining 7.5 mm was bonded so as to protrude from the sheet metal. In addition, a conductive hot melt type adhesive was used as the adhesive. Next, the surface of the rubber sheet was immersed and coated with the paint S-1 for forming a surface layer, and after air drying, it was heat-treated at a temperature of 150° C. for 1 hour to obtain a developing blade according to Example 39 having a resin layer with a thickness of 15 μm on the outer periphery of the conductive layer.
[0218] 7. Characterization [7-1] The resulting developing blade was subjected to the above-mentioned Evaluations 5-1, and 5-3 to 5-10.
[0219] [7-2]1×10 6 Hz~1×10 7 Slope in Hz, and 1×10 -2 Hz~1×10 1 Measuring impedance in Hz The impedance measurement according to the present disclosure was carried out as follows. First, as a pretreatment, platinum was vapor-deposited on the outer surface of the developing blade to create a measurement electrode. At this time, a rectangular electrode 213 mm long was created using masking tape at a location 1 mm to 6 mm from the tip of the developing blade on the side where the metal plate was not attached. Next, a conductor was attached to the electrode using silver paste and connected to the measurement electrode of an impedance measuring device (Solartron 1260 and 1296, manufactured by Toyo Technica Co., Ltd.). The impedance was measured at 23°C and 50% relative humidity with vibration voltage of 1Vpp, DC of 10V, and frequency of 10 -2 ~10 7 The impedance was measured at 1.0×10 Hz (five points were measured when the frequency changed by one digit) to obtain the absolute impedance value. The measurement results were then used to create a graph in which the absolute impedance value and frequency were plotted on a logarithmic scale. -2 ~1.0×10 1 Impedance in Hz was calculated. Next, the surface layer was peeled off from the developing blade, and platinum was vapor-deposited on the surface of the conductive layer in the same manner as above to prepare a measurement electrode. Then, the impedance was measured in the same manner as above, and a graph was created. From this graph, it was found that the frequency was 1.0×10 6 Hz~1.0×10 7 The slope in Hz was calculated. -2 ~1.0×10 1 Impedance in Hz was calculated.
[0220] [7-3] Image (fog) evaluation In order to confirm the sustained charge imparting property in the high speed process of the developing blade, the following evaluation was carried out. First, the developing blade according to Example 39 was left for 48 hours in an environment with a temperature of 23° C. and a relative humidity of 50%. Then, this developing blade was attached to a process cartridge for a laser printer (product name: Laserjet M608dn, manufactured by HP). Meanwhile, in order to evaluate the laser printer in a high-speed process, the number of sheets output per unit time was modified to 75 sheets / minute on A4 size paper, which is more than the original output number. In this case, the output speed of the recording media was set to 380 mm / sec, and the image resolution was set to 1,200 dpi. In addition, the printer was modified to enable voltage application to the voltage application electrode for the developing blade from an external power source, and the metal part of the developing sleeve and the sheet metal of the developing blade were electrically connected. This laser printer was also left in an environment with a temperature of 23°C and a relative humidity of 50% for 48 hours. Next, the process cartridge was loaded into the laser printer and left for 4 hours in an environment of 32°C temperature and 85% relative humidity, after which a process was carried out in which a solid white image with a print rate of 0% was output onto recording paper in the same environment, and the color laser printer was turned off midway through the process. At this time, the charge amount Q / M (μC / g) of the toner on the developing sleeve before passing through the nip between the photoconductor and the developing sleeve was measured. Specifically, the measurement of the toner charge amount was performed in the same manner as in the evaluation of the developing roller. For one developing sleeve, the above operation was repeated three times to measure the toner charge amount three times, and the arithmetic mean value was calculated to be the toner charge amount by the developing blade related to the evaluation target. Furthermore, when the printer was stopped while outputting a solid white image, the developer adhering to the photoconductor before transfer was removed with tape, and the reflectance R1 of the tape was measured with a reflection densitometer (product name: TC-6DS / A; manufactured by Tokyo Denshoku Co., Ltd.). The amount of decrease in reflectance "R0-R1" (%) relative to the reflectance R0 of an unused tape was calculated and used as the fog value. These fog values were ranked according to the following criteria. Rank A: The fogging value is less than 1.5%. Rank B: The fog value is 1.5% or more and less than 3.0%. Rank C: The fog value is 3.0% or more and less than 5.0%. Rank D: The fogging value is 5.0% or more.
[0221] [7-4] Toner charge amount In order to evaluate the charging ability of the developing blade to the toner, the amount of charge was measured. During the evaluation of the fog image, the toner carried on the narrow part of the developing sleeve between the developing blade and the contact position of the photoconductor was collected by suction using a metal cylindrical tube and a cylindrical filter. At that time, the amount of charge stored in the capacitor through the metal cylindrical tube and the mass of the toner sucked in were measured. The amount of charge was measured using a measuring device (product name: 8252) manufactured by ADC Corporation. From these values, the amount of charge (μC / g) per unit mass was calculated. When a negatively charged toner is used, the sign of the amount of charge per unit mass is negative, and the larger the absolute value, the higher the charging ability of the developing blade. The value obtained by measurement was taken as the amount of charge.
[0222] [7-5] Toner charge distribution In order to evaluate the spread of the charge amount of the toner, the charge amount distribution was measured. The charge distribution was measured using an E-spart Analyzer Model EST-III (manufactured by Hosokawa Micron Corporation). Except for this, the charge distribution was measured in the same manner as the toner charge measurement. The number of particles measured was about 3000. The standard deviation was calculated from the obtained charge distribution, and the obtained value was taken as the initial charge distribution of the toner. The evaluation results are shown in Tables 24 to 27.
[0223] [7-6] High temperature and humidity / low temperature and humidity cycle test A test for alternately evaluating in a high temperature / high humidity environment and a low temperature / low humidity environment (hereinafter referred to as an environmental cycle test) was conducted as follows: First, in the same manner as in the image (fog) evaluation, a magenta toner cartridge equipped with each developing blade was loaded into the laser printer, and the printer was placed in a high temperature / high humidity environment (hereinafter referred to as H / H) with an air temperature of 32°C and a relative humidity of 85% RH, and then left for 30 minutes. Next, in this environment, an image (hereinafter also referred to as "E letter image") in which the letter "E" in 4 points is printed so that the coverage rate of the area of A4 size paper is 1% was continuously output on 500 sheets of copy paper. Next, the toner cartridge and the laser printer were placed in a low temperature and low humidity environment (hereinafter referred to as L / L) with an air temperature of 15° and a relative humidity of 10% RH, and left for 30 minutes. Next, in this environment, an image (hereinafter also referred to as "E letter image") in which the letter "E" in 4 points is printed so that the coverage rate of the area of A4 size paper is 1% was continuously output on 500 sheets of copy paper. This H / H and L / L image output constituted one cycle, and a total of five cycles were repeated.
[0224] Next, the toner charge amount and the toner charge amount distribution were measured in the same manner as the measurement before the environmental cycle test. Furthermore, the developing blade was taken out of the toner cartridge, and the state of destruction near the surface layer of the developing blade was evaluated according to the following criteria. Rank A: No damage observed across the entire developing blade. Rank B: Minor damage was observed only on the edge of the developing blade (within a range of 1.5 cm from the longitudinal edge of the elastic layer). Rank C: Minor damage is observed in areas other than the edge of the developing blade. Rank D: Damage is found anywhere on the entire developing blade, causing problems in the image.
[0225] [Examples 40 to 45] [Preparation of unvulcanized rubber compositions E-39 to E-44 for domain formation] Unvulcanized rubber compositions for forming domains were prepared in the same manner as in unvulcanized rubber composition E-1 for forming domains, except that the rubbers and conductive agents shown in Table 22-1 were used.
[0226] [Table 22-1]
[0227] [Preparation of unvulcanized rubber compositions E-39 to E-44 for forming a matrix] An unvulcanized rubber composition for forming a matrix was prepared in the same manner as in the unvulcanized rubber composition for forming a matrix E-1, except that the rubbers shown in Table 22-2 were used.
[0228] [Table 22-2]
[0229] In addition, "Zeospan" in the above table is the trade name of a polyether-based synthetic rubber manufactured by Zeon Corporation.
[0230] [Preparation of Unvulcanized Rubber Compositions E-39 to E-44 for Forming Conductive Layer] Unvulcanized rubber compositions E-39 to E-44 for forming a conductive layer were prepared in the same manner as unvulcanized rubber composition E-1 for forming a conductive layer, except that unvulcanized rubber compositions E-39 to E-44 for forming a domain, unvulcanized rubber compositions E-39 to E-44 for forming a matrix, and other materials were mixed in the blending ratios shown in Table 22-3.
[0231] [Table 22-3]
[0232] [Making the development blade] A rubber sheet was prepared in the same manner as in Example 39, except that the conductive layer-forming unvulcanized rubber compositions E-39 to E-44 were used, and the prepared rubber sheet was adhered to a metal plate. Next, a surface layer was formed on the surface of the rubber sheet in the same manner as in Example 39, except that the coating material for forming a surface layer shown in Table 23 was used, to obtain developing blades according to Examples 40 to 45.
[0233] [Examples 46 to 50] Except for changing the coating material for forming the surface layer to that shown in Table 23, the same procedure as in Comparative Example 44 was carried out to obtain developing blades according to Examples 46 to 50.
[0234] [Table 23]
[0235] [Comparative Examples 15 to 19] [Preparation of unvulcanized rubber compositions EC-13 to EC-17 for domain formation] Except for using the rubbers and conductive agents shown in Table 24-1, unvulcanized rubber compositions for forming domains were prepared in the same manner as in unvulcanized rubber composition E-1 for forming domains.
[0236] [Table 24-1]
[0237] [Preparation of unvulcanized rubber compositions for matrix formation EC-15 to EC-17] An unvulcanized rubber composition for forming a matrix was prepared in the same manner as in the unvulcanized rubber composition for forming a matrix E-1, except that the rubbers shown in Table 24-2 were used.
[0238] [Table 24-2]
[0239] [Preparation of Unvulcanized Rubber Compositions EC-13 to E-17 for Forming Conductive Layer] Unvulcanized rubber compositions for forming a conductive layer EC-13 to EC-17 were prepared in the same manner as unvulcanized rubber composition for forming a conductive layer E-1, except that the unvulcanized rubber composition for forming a domain, the unvulcanized rubber composition for forming a matrix, and other materials were mixed in the blending ratios shown in Table 24-3.
[0240] [Table 24-3]
[0241] [Making the development blade] A rubber sheet was prepared in the same manner as in Example 39, except that the conductive layer-forming unvulcanized rubber compositions EC-13 to EC-17 were used, and the prepared rubber sheet was bonded to a metal plate. Next, a surface layer was formed on the surface of the rubber sheet in the same manner as in Example 39, except that the coating material for forming a surface layer shown in Table 25 was used, to obtain development blades according to Comparative Examples 15 to 19.
[0242] [Comparative Examples 20 and 21] Developing blades according to Comparative Examples 20 and 21 were obtained in the same manner as in Example 39, except that the coating material for forming the surface layer was changed to that shown in Table 25.
[0243] [Table 25]
[0244] The evaluation results of the developing blades according to Examples 39 to 49 and Comparative Examples 15 to 22 are shown in Tables 26-1 to 26-3 and Tables 27-1 to 27-3.
[0245] [Table 26-1]
[0246] [Table 26-2]
[0247] [Table 26-3]
[0248] [Table 27-1]
[0249] [Table 27-2]
[0250] [Table 27-3]
[0251] The developing blades according to Examples 39 to 50 had a matrix domain structure according to the present disclosure in the conductive layer. The impedance in the low frequency range measured between the outer surface of the developing blade and the outer surface of the support was 1.0×10 4 ~1.0×10 11 Because the toner has a thickness of Ω, the charge distribution is sharp and the fog value is very small, resulting in high-quality images. Furthermore, in Examples 39 to 49, in which the surface layer is made of urethane resin, no damage occurs near the surface even after the environmental cycle test, and the toner maintains a sharp charge distribution and good image characteristics. In contrast, in the development blades of Comparative Examples 15 to 19, which do not have the conductive layer of the present disclosure, and Comparative Examples 20 and 21, in which the impedance in the low frequency range measured between the outer surface of the development blade and the outer surface of the support is outside the range of the present disclosure, the charge distribution was large and the image quality was not good.
[0252] [Example 51] [Preparation of Surface Layer Forming Paint 17] Under a nitrogen atmosphere, 100 parts by mass of polyester polyol (product name: P3010, manufactured by Kuraray Co., Ltd.) was gradually added dropwise to 27 parts by mass of polymeric MDI (product name: Millionate MR200, manufactured by Nippon Polyurethane Industry Co., Ltd.) in a reaction vessel while maintaining the temperature inside the reaction vessel at 65° C. After completion of the dropwise addition, the mixture was allowed to react at a temperature of 65° C. for 2 hours. The resulting reaction mixture was cooled to room temperature to obtain an isocyanate-terminated prepolymer with an isocyanate group content of 4.3%.
[0253] Mixture 1 was prepared by dissolving 54.9 parts by mass of the obtained isocyanate group-terminated prepolymer in methyl ethyl ketone (MEK) with 41.52 parts by mass of polyester polyol (product name: P2010, manufactured by Kuraray Co., Ltd.) and 23 parts by mass of carbon black (MA230: manufactured by Mitsubishi Chemical Corporation, number average particle diameter 30 nm) to a solid content of 27% by mass. In a 450 mL glass bottle, 270 g of the mixed solution 1 and 200 g of glass beads with an average particle size of 0.8 mm were placed and dispersed for 12 hours using a paint shaker disperser. Next, 15 parts by mass of urethane particles with an average particle size of 7.0 μm (Dymic Beads UCN-5070D: manufactured by Dainichiseika Chemicals Co., Ltd.) were added and dispersed for another 15 minutes. After that, the glass beads were removed to obtain a coating material 17 for forming a surface layer.
[0254] [Preparation of charging roller] A conductive layer was formed on the circumferential surface of the core bar in the same manner as in Example 2, except that the conductive layer was shaped like a crown, with a diameter of 9.65 mm at each position 90 mm from the center to both ends and a central diameter of 9.70 mm. Next, the surface layer forming paint 17 was applied onto the conductive layer in the same manner as in Example 1. After application, the paint was air-dried at a temperature of 23°C for 30 minutes, then dried in a hot air circulation dryer at a temperature of 80°C for 1 hour, and further dried at a temperature of 160°C for 1 hour, to form a dry film of the coating of the surface layer forming paint 17 on the elastic layer.
[0255] Furthermore, the outer surface of the dried film was irradiated with ultraviolet light having a wavelength of 254 nm with an integrated light amount of 9000 mJ / cm 2The outermost skin layer of the dry film was removed to form a surface layer in which the conductive particles (carbon black) in the dry film were exposed to the outer surface. A low-pressure mercury lamp (manufactured by Toshiba Lighting & Technology Corporation) was used as the source of ultraviolet light. In this way, an electrophotographic roller 51 according to Example 51 was produced.
[0256] 8. Evaluation as a charging roller The obtained electrophotographic roller 51 was evaluated as follows. [8-1] Measurement of volume resistivity of surface layer The volume resistivity of the surface layer was measured in a conductive mode using an atomic force microscope (AFM) (product name: Q-scope250:, Quesant). First, the surface layer of the electrophotographic roller 51 was cut into a sheet with a width of 2 mm and a length of 2 mm using a manipulator, and platinum was deposited on one side of the surface layer. Next, a direct current power source (product name: 6614C, Agilent) was connected to the platinum-deposited surface, 10 V was applied, and the free end of the cantilever was brought into contact with the other side of the surface layer, and a current image was obtained through the AFM body. This measurement was performed on 100 randomly selected points on the surface of the entire surface layer, and the "volume resistivity" was calculated from the average current value of the top 10 lowest current values and the average film thickness of the surface layer. The measurement conditions are as follows. Measurement mode: contact Cantilever: CSC17 Measurement range: 10nm x 10nm Scan rate: 4Hz Applied voltage: 10V
[0257] [8-2] Frequency 1×10 6 Hz~1×10 7 Impedance slope in Hz and frequency 1×10 -2 Hz~1×10 1 Calculating impedance values in Hz As in the previous evaluation [5-2], the frequency of the conductive layer was 1 × 10 6 Hz~1×10 7 Impedance slope in Hz, 1×10 -2Hz~1×10 1 The impedance value in Hz and the frequency 1×10 measured by applying a predetermined AC voltage between the outer surface of the electrophotographic roller and the conductive outer surface of the support are -2 Hz~1×10 1 The impedance was calculated in Hz.
[0258] [8-3] Measurement of surface layer thickness The thickness of the surface layer was measured by observing a cross section of the surface layer at nine locations (three axial locations and three circumferential locations) with an optical microscope or an electron microscope, and the average value was taken as the "thickness" of the surface layer.
[0259] [8-4] Measurement of universal hardness of surface layer The universal hardness at a position 1 μm deep from the surface of the surface layer was measured by a universal hardness tester. For the measurement, an ultra-microhardness tester (product name: FISCHERSCOPE HM-2000, manufactured by Helmut Fischer) was used. Specific measurement conditions are shown below. Measurement indenter: Vickers indenter (face angle 136, Young's modulus 1140, Poisson's ratio 0.07, indenter material: diamond) Measurement environment: Temperature 23°C, relative humidity 50% Maximum test load: 1.0mN Loading conditions: Load was applied proportional to time at a rate that reached the maximum test load in 30 seconds. In this evaluation, the universal hardness was calculated according to the following formula (1) using the load F at the time when the indenter was pressed to a depth of 1 μm from the surface of the surface layer and the contact area A between the indenter and the surface layer at that time. Calculation formula (1) Universal hardness (N / mm 2 )=F / A
[0260] [8-5] Measurement of protrusions originating from exposed areas of electronic conductive material on the surface layer The method for measuring the number of protrusions resulting from the exposed portion of the electronic conductive agent particles on the surface of the surface layer is as follows. First, the elastic layer including the surface layer is cut out from the electrophotographic roller 51, platinum is evaporated onto the outermost surface of the surface layer, and an area of 2.0 μm in length × 2.0 μm in width is observed at 40,000 times magnification using a scanning electron microscope (product name: S-4800, manufactured by Hitachi High-Technologies Corporation) and photographed. The obtained image is analyzed using image analysis software (product name: Image-Pro Plus, manufactured by Planetron Corporation). The photographed SEM image is subjected to binarization processing to calculate the number of protrusions. Five SEM images are photographed, and the average of the calculated particle numbers is taken as the number of fine protrusions.
[0261] [8-6] Toner charge evaluation When the electrophotographic roller 1 was used as a charging roller, the negative charge supplying capability to contaminants (contaminants such as transfer residual toner and external additives) was evaluated as follows. A laser printer (product name: HP LaserJet P1505 Printer, manufactured by HP) was prepared as the electrophotographic image forming apparatus. The print speed of this laser printer was 23 pages / minute, and the image resolution was 600 dpi. However, for this evaluation, the motor of this laser printer was modified so that the process speed was 1.2 times faster than normal. Furthermore, an external power source was connected to apply voltage to the charging roller, and the printer was modified so that voltage was not applied directly to the charging roller from the main body. Furthermore, a process cartridge for this laser printer (product name: "HP 36A (CB436A)", manufactured by HP) was modified by removing the cleaning blade for the charging roller, the developing container that contacts the photosensitive drum, and the transfer roller. The laser printer and the process cartridge were left in a low-temperature, low-humidity environment (temperature 15°C, relative humidity 10%) for 48 hours. The process cartridge was then loaded into the laser printer. The following evaluations were then performed in the low-temperature, low-humidity environment. In a low-temperature, low-humidity environment, charge injection from the electrophotographic member to the toner is unlikely to occur. By performing the following evaluations in such an environment, the ability of the electrophotographic member to inject charge into the toner can be more accurately evaluated. First, the main body was stopped midway through an image forming process in which one solid black image was output under normal image output conditions, and a state was formed in which the entire circumference of the photosensitive drum was covered with a toner layer. Next, the process cartridge in which the entire circumference of the photosensitive drum was covered with a toner layer was removed from the main body. The charging roller of this process cartridge was removed, and the electrophotographic roller 1 was attached as the charging roller. This process cartridge was then attached to the main body. Then, an image forming process was performed in which a voltage at which the electrophotographic roller 1 would not discharge, specifically -500V, was applied to the electrophotographic roller 1 from an external power source to output one solid white image, and during this process, the potential of the toner on the surface of the toner layer on the photosensitive drum was measured before and after passing through the nip portion between the electrophotographic roller 1 and the photosensitive drum. The potential was measured using a surface potential meter probe (product name: MODEL555P-1, manufactured by Trek Japan) placed 2 mm away from the photosensitive drum surface. The difference between the potential of the surface of the toner layer before passing through the nip portion and the potential of the surface of the toner layer after passing through the nip portion was measured as the amount of charge (V) injected by the conductive member. This evaluation was carried out at low temperature and low humidity (temperature 15°C, relative humidity 10%). A laser beam printer (product name: HP LaserJet P1505 Printer, manufactured by HP) was prepared as the electrophotographic device. This laser beam printer is capable of printing A4 size paper in the vertical direction. The print speed is 23 sheets / minute, and the image resolution is 600 dpi. In this evaluation, the laser beam printer was modified so that the process speed was 1.2 times faster than normal. In addition, an external power source was connected to apply a voltage to the charging roller, so that the voltage was not applied directly from the main body to the charging roller. Furthermore, the transfer roller was also removed. The cleaning blade was removed from the process cartridge for the laser printer (product name: "HP 36A (CB436A)", manufactured by HP). This process cartridge was loaded into the laser printer body, and while outputting a solid black image, the lid of the body was opened and stopped just before development and transfer occurred, and a certain amount of toner was placed on the photosensitive drum. Next, the process cartridge was removed from the laser printer body, the charging roller attached to the process cartridge was removed, and the electrophotographic roller 51 was attached so that the part of the photosensitive drum on which the toner was placed would abut against the adjacent part. This allowed the charging roller to come into contact with the toner on the drum immediately after starting image output. This process cartridge was loaded again into the laser printer body. Then, a surface potential meter probe (product name: MODEL555P-1, manufactured by Trek Japan) was placed at a position 90 degrees rotated in the circumferential direction of the photosensitive drum from the position of the electrophotographic roller 51 and 2 mm away from the photosensitive drum. In this state, a solid white image was output. At this time, -500V was applied so that no discharge would occur from the electrophotographic roller, and the electrophotographic roller 51 was brought into contact with the toner to inject charge. The potential of the toner-carrying portion of the drum in contact with the electrophotographic roller 51 was measured and used as the charge amount. The greater the absolute value of the potential, the greater the amount of charge injected into the toner.
[0262] [8-7] Dirt evaluation test A gear rotating at a peripheral speed difference of 110% in the forward direction relative to the rotation of the photosensitive drum was attached to the charging roller of the electrophotographic roller 51. This electrophotographic roller 51 was attached as a charging roller to a process cartridge (product name: "HP 36A (CB436A)", manufactured by HP) from which the charging roller and cleaning blade had been removed. This process cartridge was loaded into the laser beam printer body, and 500 images were printed out at a process speed 1.2 times faster than normal, depicting horizontal lines with a width of 2 dots and an interval of 100 dots in the direction perpendicular to the direction of rotation of the photosensitive drum. Next, the electrophotographic roller 51 was removed from the process cartridge, and the following evaluations were performed. After attaching polyester adhesive tape (product name: No. 31B, manufactured by Nitto Denko Corporation) to the outer surface of the removed electrophotographic roller 51, the adhesive tape was peeled off together with the toner adhering to the surface of the charging roller, and attached to a blank sheet of paper. After this was performed for the entire image printing area on the surface of the charging roller, the reflection density of the adhesive tape was measured for the entire image printing area using a Photovoltaic reflection densitometer (product name: TC-6DS / A, manufactured by Tokyo Denshoku Co., Ltd.) to determine the maximum value. Next, the reflection density of a new polyester adhesive tape attached to a blank sheet of paper was measured to find the minimum value, and the increase in reflection density was taken as the color density value. The smaller the color density value, the less dirt there was on the charging roller, which means it was in a good condition, so this was used as an index of the degree of dirt on the charging roller.
[0263] [8-8] Stable charging evaluation test In a main body and cartridge configuration similar to those of 8-5, 20,000 images were printed on A4 size paper in a low temperature and low humidity environment (temperature 15°C, relative humidity 10%), with the letter "E" in 4-point size printed on the paper at a print rate of 1%. The output of the electrophotographic image was performed in a so-called intermittent mode, in which the rotation of the electrophotographic photosensitive member was stopped for 7 seconds after each output of the electrophotographic image. Compared to the case of continuously outputting electrophotographic images, the image output in the intermittent mode is a harsher evaluation condition for the charging roller because the number of times the charging roller rubs against the electrophotographic photosensitive member is greater. Next, a halftone image was output, and the resulting image was evaluated according to the following criteria. A: There are no white spots on the output image, even when viewed with a magnifying glass. B: No white spots are visually observed on the output image. C: Slight white spots are observed on the output image. D: White spots are observed over the entire output image.
[0264] [Examples 52 to 56] [Preparation of Surface Layer Forming Coatings 18 to 22] Coatings 18 to 22 for forming surface layer were prepared in the same manner as coating material 17 for forming surface layer, except that the materials shown in Table 28 were used in the amounts shown in Table 28.
[0265] [Table 28]
[0266] The symbols in Table 28 represent the following materials. A-1: Polyester polyol (product name: P2010, manufactured by Kuraray) A-2: Polycarbonate-based (product name: T5652, manufactured by Asahi Kasei Chemicals Corporation) A-3: Acrylic polyol (product name: DC2016, manufactured by Daicel Chemical Industries, Ltd.) B-1: Polyester polyol / polymeric MDI (product name: P3010 manufactured by Kuraray Co., Ltd. / product name: Millionate MR200 manufactured by Nippon Polyurethane Industry Co., Ltd.) B-2: Polycarbonate polyol / polymeric MDI (product name: T5652 manufactured by Asahi Kasei Chemicals Corporation / product name: Millionate MR200 manufactured by Nippon Polyurethane Industry Co., Ltd.) B-3: Isocyanate A / Isocyanate B=4:3 (Product name: Bestanate B1370 manufactured by Degussa Corporation / Product name: Duranate TPA-880E manufactured by Asahi Kasei Chemicals Corporation) C-1: Urethane beads (product name: Dimic Beads UCN-5070D, manufactured by Dainichiseika Chemicals Co., Ltd., average particle size 7.0 μm) D-1: Modified dimethyl silicone oil (product name: SH-28PA, manufactured by Toray Dow Corning Silicone Co., Ltd.)
[0267] [Electrophotographic rollers 52-56] Electrophotographic rollers 52 to 56 were produced and evaluated in the same manner as in Example 51, except that the coating materials 18 to 22 for forming the surface layer were used.
[0268] [Example 57] The cumulative amount of ultraviolet light is 450 mJ / cm 2An electrophotographic roller 57 according to Example 57 was produced and evaluated in the same manner as in Example 51, except that the above-mentioned conditions were met.
[0269] [Example 58] An electrophotographic roller 58 according to Example 58 was produced and evaluated in the same manner as in Example 51, except that ultraviolet irradiation was not performed.
[0270] [Comparative Example 22] The outer shape of the conductive layer EC-1 according to Comparative Example 1 was a crown shape with a diameter of 9.65 mm at each position 90 mm from the center to both ends in the longitudinal direction, and a central diameter of 9.70 mm. In addition, the surface layer forming paint 17 was used. Except for the above, an electrophotographic roller according to Comparative Example 22 was produced and evaluated in the same manner as in Comparative Example 1. The electrophotographic roller does not have a matrix-domain structure in the conductive layer. As a result of evaluation as a charging roller, the amount of charge was low, the amount of dirt was large, and white spots were also observed.
[0271] [Comparative Example 23] The outer shape of the conductive layer EC-4 according to Comparative Example 4 was a crown shape with a diameter of 9.65 mm at each position 90 mm from the center to both ends in the longitudinal direction, and a central diameter of 9.70 mm. In addition, the surface layer forming paint 17 was used. Except for these, an electrophotographic roller according to Comparative Example 23 was produced and evaluated in the same manner as in Comparative Example 4. In this electrophotographic roller, the conductive layer has a matrix-domain structure, but the impedance of the conductive layer in the high frequency range was outside the range of the present disclosure. As a result of the evaluation as a charging roller, the charge amount was low, the amount of dirt was large, and the occurrence of white spots was also observed. The results of Evaluation 8 above are shown in Table 29.
[0272] [Table 29] [Explanation of symbols]
[0273] 1A Electrophotographic roller 1B Electrophotographic Blade 2 Support 3 Conductive layer 4 Surface layer 6a Domain 6b Matrix
Claims
1. A conductive member for electrophotography comprising a support having a conductive outer surface, a conductive layer provided on the outer surface of the support, and a surface layer provided on the outer surface of the conductive layer, the conductive layer has a matrix containing a crosslinked product of a first rubber and a plurality of domains dispersed in the matrix, The domain comprises a crosslinked product of a second rubber and an electronic conductive agent, After the surface layer was peeled off, a platinum electrode was directly provided on the outer surface of the conductive layer, and an AC voltage with an amplitude of 1 V and a frequency of 1.0×10 was applied between the outer surface of the support and the platinum electrode in an environment of a temperature of 23° C. and a relative humidity of 50%. -2 Hz ~ 1.0 x 10 7 The impedance was measured by applying a voltage varying between 1.0 and 1.0 Hz. The frequency was plotted on the horizontal axis and the impedance on the vertical axis in logarithmic scale. 6 Hz ~ 1.0 x 10 7 The slope in Hz is −0.8 or more and −0.3 or less, and the frequency is 1.0×10 -2 Hz ~ 1.0 x 10 1 Impedance at Hz is 1.0 x 10 4 ~1.0 x 10 11 Ω and A platinum electrode was directly provided on the outer surface of the conductive member, and an AC voltage with an amplitude of 1 V and a frequency of 1.0×10 was applied between the outer surface of the support and the platinum electrode in an environment of a temperature of 23° C. and a relative humidity of 50%. -2 Hz ~ 1.0 x 10 7 The impedance was measured by applying a voltage varying between 1.0 × 10 Hz. The frequency was plotted on the horizontal axis and the impedance on the vertical axis in logarithmic scale. -2 Hz ~ 1.0 x 10 1 Impedance at Hz is 1.0 x 10 5 ~1.0 x 10 11 Ω, A conductive member comprising:
2. The conductive member according to claim 1 , wherein the conductive layer is disposed directly on the outer surface of the support.
3. The conductive resin layer is further provided between the conductive layer and the outer surface of the support, and after the surface layer and the conductive layer are peeled off, a platinum electrode is provided directly on the outer surface of the resin layer, and an AC voltage with an amplitude of 1 V and a frequency of 1.0×10 is applied between the outer surface of the support and the platinum electrode in an environment of a temperature of 23° C. and a relative humidity of 50%. -2 Hz ~ 1.0 x 10 7 The impedance was measured by applying a voltage varying between 1.0 × 10 Hz. The frequency was plotted on the horizontal axis and the impedance on the vertical axis in logarithmic scale. -2 Hz ~ 1.0 x 10 1 Impedance at Hz is 1.0 x 10 -5 ~1.0 x 10 1 The conductive member according to claim 1, wherein the resistance is Ω.
4. The volume resistivity of the matrix is 1.0×10 12 Ωcm or more, 1.0×10 17 The conductive member according to any one of claims 1 to 3, having a resistivity of Ωcm or less.
5. 5. The conductive member according to claim 1, wherein an arithmetic mean value Dm of the distance between adjacent domains is 0.2 μm or more and 2.0 μm or less.
6. The conductive member according to any one of claims 1 to 5, wherein, when a length in the longitudinal direction of the conductive layer is L and a thickness of the conductive layer is T, observation regions of 15 µm square are placed at any three locations in a thickness region from an outer surface of the conductive layer to a depth of 0.1T to 0.9T for each of a cross section of the conductive layer in the thickness direction at the center in the longitudinal direction of the conductive layer and three locations at L / 4 from both ends of the conductive layer toward the center, 80% by number or more of domains observed in each of all nine observation regions satisfy the following requirement (1) and requirement (2): (1) The ratio of the cross-sectional area of the electronic conductive agent contained in the domain to the cross-sectional area of the domain is 20% or more; (2) When the perimeter of a domain is A and the envelope perimeter of the domain is B, A / B is 1.00 or more and 1.10 or less.
7. The conductive member according to any one of claims 1 to 6, wherein μ is an average value of a ratio of a cross-sectional area of the electronic conductive agent contained in each of the domains to a cross-sectional area of each of the domains appearing in a cross section in the thickness direction of the conductive layer, and σ is a standard deviation of the ratio, σ / μ is 0 to 0.4, and μ is 20% to 40%, and at least 8 of sample cubes having a cubic shape with one side of 9 μm sampled from any 9 positions on the conductive layer satisfy the following requirement (3): (3) A sample cube is divided into 27 unit cubes each having a side length of 3 μm, and the volume Vd of the domain contained in each unit cube is calculated. Vd is 2.7 μm 3 ~10.8μm 3 There must be at least 20 unit cubes in which
8. The conductive member according to any one of claims 1 to 7, wherein the surface layer contains at least one kind of binder resin and at least one kind of electronic conductive agent and ionic conductive agent.
9. The conductive member according to claim 8 , wherein the binder resin is a urethane resin.
10. The conductive member according to claim 9 , wherein the urethane resin has a urethane group concentration of 1.5% or more and 6.5% or less.
11. The conductive member according to claim 9 or 10, wherein the urethane resin has at least one structure selected from the group consisting of structures represented by structural formulas (1) to (3). [Case 1] In structural formulas (1) to (3), R 1 ~R 3 each independently represents a linear or branched divalent hydrocarbon group having 4 to 8 carbon atoms.
12. The surface layer contains a binder resin and an electronic conductive agent, the surface has convex portions resulting from exposed portions of the electronic conductive agent, and the universal hardness at a position 1 μm deep from the surface is 1.0 N / mm 2 Above, 7.0N / mm 2 The conductive member according to any one of claims 1 to 11, wherein:
13. The volume resistivity of the surface layer is 1.0×10 4 Ω・cm or more, 1.0×10 15 The conductive member according to any one of claims 1 to 12, having a resistivity of Ω·cm or less.
14. The conductive member according to any one of claims 1 to 13, wherein the surface layer contains roughening particles having a number average particle diameter of 3 µm or more and 30 µm or less, and has protrusions on the surface thereof derived from the roughening particles.
15. A conductive member described in any one of claims 1 to 14, wherein the first rubber is at least one rubber selected from the group consisting of natural rubber, butadiene rubber, butyl rubber, acrylonitrile butadiene rubber, urethane rubber, silicone rubber, fluororubber, chloroprene rubber, styrene-butadiene rubber, ethylene-propylene rubber, and polynorbornene rubber.
16. The conductive member according to any one of claims 1 to 15, wherein a difference in absolute values of solubility parameters between the first rubber and the second rubber is 0.4 (J / cm 3 ) 0.5 or more and 5.0 (J / cm 3 ) 0.5 or less.
17. The conductive member described in claim 16, wherein the second rubber is at least one rubber selected from the group consisting of natural rubber, butadiene rubber, styrene-butadiene rubber, butyl rubber, ethylene-propylene rubber, chloroprene rubber, nitrile rubber, hydrogenated nitrile rubber, silicone rubber, and urethane rubber.
18. A conductive member described in any one of claims 15 to 17, wherein the first rubber is styrene-butadiene rubber and the second rubber is acrylonitrile butadiene rubber.
19. 19. A process cartridge configured to be detachably mountable to a main body of an electrophotographic image forming apparatus, comprising the conductive member according to claim 1.
20. 19. An electrophotographic image forming apparatus comprising the conductive member according to claim 1.
Citation Information
Patent Citations
Electrifying member, and image forming apparatus and process cartridge using the same
JP2004151695A
Conductive roll and inspection method therefor
JP2006207807A
Conductive member, charging device, process cartridge, and image forming device
JP2011022410A
Image forming apparatus
JP2014153488A
Conductive member for electrophotographic apparatus
JP2017015800A
